Toner, developer, toner storage unit, image forming apparatus, and image forming method

JP7651837B2Active Publication Date: 2025-03-27RICOH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020178189
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-23
Publication Date
2025-03-27
Estimated Expiration
2040-10-23

AI Technical Summary

Benefits of technology

【0007】 本発明の一態様は、優れた、低温定着性、耐高温オフセット性、耐熱保存性及び帯電性を有するトナーを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651837000007
    Figure 0007651837000007
  • Figure 0007651837000008
    Figure 0007651837000008
  • Figure 0007651837000009
    Figure 0007651837000009
Patent Text Reader

Abstract

To provide toner having excellent low-temperature fixability, high-temperature offset resistance, heat-resistant storage stability and chargeability.SOLUTION: Toner according to the present invention includes: toner base particles containing binder resin; organic resin fine particles having a core-shell structure, on a surface of the toner base particles, comprised of a core having a resin (a) containing a styrene-acrylic resin but not containing a carboxyl group, and a shell having a resin (b) containing a carboxyl group; and an anionic surfactant containing the carboxyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner, a developer, a toner storage unit, an image forming apparatus, and an image forming method. [Background technology]

[0002] Image forming devices using toner, such as multi-function peripherals (MFPs) and printers, are widely used in various places, including offices. Toner is required to have high-temperature offset resistance, low-temperature fixing property, and heat-resistant storage property in order to improve the quality of output images, reduce power consumption during fixing to save energy, and increase resistance to high temperatures and high humidity during storage and transportation.

[0003] As a toner with improved high-temperature offset resistance, low-temperature fixing property, and heat-resistant storage stability, for example, a toner containing resin fine particles having a weight average molecular weight (Mw) of 8,000 to 1,000,000 and a particle size of 20 to 400 nm and having a core-shell structure has been proposed (see, for example, Patent Document 1). Summary of the Invention [Problem to be solved by the invention]

[0004] However, the toner of Patent Document 1 does not consider improving the charging performance. If the charging property of the toner is reduced, there is a possibility that background scumming or scattering of the toner may occur. Therefore, in order to further utilize the toner, a toner excellent in all of low-temperature fixing property, high-temperature offset resistance, heat-resistant storage stability, and charging property is desired.

[0005] An object of one aspect of the present invention is to provide a toner having excellent low-temperature fixing property, high-temperature offset resistance, heat-resistant storage stability and chargeability. [Means for solving the problem]

[0006] One embodiment of the toner according to the present invention comprises toner base particles containing a binder resin, and has, on the surface of the toner base particles, organic resin fine particles having a core-shell structure composed of a core having a resin (a) that contains a styrene-acrylic resin and does not contain a carboxyl group and a shell having a resin (b) that contains a carboxyl group, and an anionic surfactant containing a carboxyl group. Effect of the Invention

[0007] An aspect of the present invention can provide a toner having excellent low-temperature fixing property, high-temperature offset resistance, heat-resistant storage stability and chargeability. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment. [Diagram 2] FIG. 2 is a schematic configuration diagram illustrating another example of an image forming apparatus according to an embodiment. [Diagram 3] FIG. 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment. [Figure 4] FIG. 4 is a partial enlarged view of the image forming apparatus of FIG. [Diagram 5] FIG. 2 is a schematic diagram illustrating an example of a process cartridge according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the embodiments are not limited by the following description, and can be modified as appropriate without departing from the gist of the present invention. In addition, in this specification, a tilde "~" indicating a numerical range means that the numerical values ​​before and after it are included as the lower and upper limits, unless otherwise specified.

[0010] <Toner> The toner according to the embodiment is a toner containing toner base particles including a binder resin, and contains organic resin particles having a core-shell structure and an anionic surfactant containing a carboxyl group on the surface of the toner. The toner according to the embodiment may contain other components such as a colorant, a release agent, etc., in addition to the binder resin, as necessary.

[0011] [Binding resin] The binder resin may include a polyester resin. The toner according to an embodiment may contain a binder resin other than the polyester resin.

[0012] (polyester resin) The polyester resin preferably contains at least one of a crystalline polyester resin and an amorphous polyester resin.

[0013] (Crystalline polyester resin) Because of its crystallinity, the crystalline polyester resin exhibits a thermal melting characteristic that shows a rapid viscosity drop near the fixing start temperature. By using a crystalline polyester resin having such characteristics together with a non-crystalline polyester resin, the heat-resistant storage stability is good due to the crystallinity until just before the melting start temperature, and at the melting start temperature, the crystalline polyester resin melts and causes a rapid viscosity drop, which leads to compatibility with the non-crystalline polyester resin, and both are fixed by a rapid viscosity drop, resulting in a toner that has both good heat-resistant storage stability and low-temperature fixing ability. In addition, the release width (the difference between the minimum fixing temperature and the high-temperature offset occurrence temperature) also shows good results.

[0014] The crystalline polyester resin is obtained by using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester. In the present embodiment, the crystalline polyester resin refers to a resin obtained by using the above components, and does not include a resin obtained by modifying a polyester resin, such as a prepolymer, which will be described later, and a resin obtained by subjecting a prepolymer to a crosslinking and / or elongation reaction.

[0015] -Polyhydric alcohol- The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.

[0016] Examples of the diol include saturated aliphatic diols. Examples of the saturated aliphatic diol include linear saturated aliphatic diols and branched saturated aliphatic diols. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. In addition, if the carbon number of the saturated aliphatic diol exceeds 12, it becomes difficult to obtain a practical material. It is more preferred that the carbon number is 12 or less.

[0017] Examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanedecanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of high crystallinity of the crystalline polyester resin and excellent sharp melt properties.

[0018] Examples of trihydric or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0019] -Polycarboxylic acids- The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include divalent carboxylic acids and trivalent or higher carboxylic acids.

[0020] Examples of the divalent carboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid; and further, anhydrides of these acids and lower (carbon number: 1 to 3) alkyl esters of these acids.

[0021] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower (carbon number 1 to 3) alkyl esters thereof.

[0022] The polycarboxylic acid may contain a dicarboxylic acid having a sulfonic acid group in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. The polycarboxylic acid may contain a dicarboxylic acid having a double bond in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. These may be used alone or in combination of two or more.

[0023] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms. That is, the crystalline polyester resin preferably has a constitutional unit derived from a saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a constitutional unit derived from a saturated aliphatic diol having 2 to 12 carbon atoms. This is preferable in that the resin has high crystallinity and excellent sharp melting properties, and can therefore exhibit excellent low-temperature fixability.

[0024] The melting point of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 60° C. to 80° C. If the melting point is less than 60° C., the crystalline polyester resin is likely to melt at low temperatures, and the heat-resistant storage stability of the toner may decrease, whereas if the melting point exceeds 80° C., the crystalline polyester resin is not sufficiently melted by heating during fixing, and the low-temperature fixability may decrease.

[0025] The molecular weight of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint that a low molecular weight resin with a sharp molecular weight distribution has excellent low-temperature fixability and that a large amount of low molecular weight components reduces heat-resistant storage stability, the weight average molecular weight (Mw) of the crystalline polyester resin soluble in orthodichlorobenzene is preferably 3,000 to 30,000, more preferably 5,000 to 15,000, as measured by gel permeation chromatography (GPC). The number average molecular weight (Mn) is preferably 1,000 to 10,000, more preferably 2,000 to 10,000. The Mw / Mn is preferably 1.0 to 10, more preferably 1.0 to 5.0.

[0026] The acid value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of affinity between paper and resin, in order to achieve the desired low-temperature fixability, it is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, while in order to improve high-temperature offset resistance, it is preferably 45 mgKOH / g or less.

[0027] The hydroxyl value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose. In order to achieve the desired temperature fixing property and good charging characteristics, the hydroxyl value is preferably 0 mgKOH / g to 50 mgKOH / g, and more preferably 5 mgKOH / g to 50 mgKOH / g.

[0028] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 One method is to detect a crystalline polyester resin that has absorption based on the δCH (out-of-plane bending vibration) of olefin.

[0029] The content of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 3 to 20 parts by mass, more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the toner. If the content is less than 3 parts by mass, the sharp melting by the crystalline polyester resin is insufficient, and the low-temperature fixing property may be poor. If the content exceeds 20 parts by mass, the heat-resistant storage stability may decrease and the image may easily become foggy. If the content is within the above more preferred range, it is advantageous in that both high image quality and low-temperature fixing property are excellent.

[0030] ((Non-crystalline polyester resin)) The amorphous polyester resin contains, as its constituent components, a diol component and a crosslinking component.

[0031] The diol component contained in the non-crystalline polyester resin contains an aliphatic diol having 3 to 10 carbon atoms in an amount of 50 mol % or more, preferably 80 mol % or more, and more preferably 90 mol % or more. It is more preferable that the content is 100% or more.

[0032] Examples of the aliphatic diol having 3 to 10 carbon atoms include 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol.

[0033] In the non-crystalline polyester resin, it is preferable that the main chain of the diol component has an odd number of carbon atoms, and the diol component has an alkyl group on the side chain.

[0034] The aliphatic diol having 3 to 10 carbon atoms preferably has an odd number of carbon atoms in the main chain and has an alkyl group in the side chain, and is preferably an aliphatic diol represented by the following general formula (1). HO-(CR 1 R 2 ) n -OH...General formula (1) In the general formula (1), R 1 , and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; n represents an odd number from 3 to 9. In the n repeating units, R 1 and R 2 may be the same or different.

[0035] The crosslinking component contained in the non-crystalline polyester resin contains a trihydric or higher aliphatic alcohol, and preferably contains a trihydric to tetrahydric aliphatic alcohol from the viewpoint of the gloss and image density of the fixed image. The crosslinking component may be only a trihydric or higher aliphatic alcohol.

[0036] Examples of trihydric or higher aliphatic alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, and dipentaerythritol. Thor and others.

[0037] The proportion of the crosslinking component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass to 5% by mass, and more preferably 1% by mass to 3% by mass.

[0038] The proportion of trihydric or higher aliphatic alcohol in the polyhydric alcohol component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50% by mass to 100% by mass, more preferably 90% by mass to 100% by mass.

[0039] The dicarboxylic acid component preferably contains an aliphatic dicarboxylic acid having 4 to 12 carbon atoms, and more preferably contains 50 mol % or more of an aliphatic dicarboxylic acid having 4 to 12 carbon atoms.

[0040] The dicarboxylic acid component preferably contains less than 60 mol % of an aliphatic dicarboxylic acid having 4 to 12 carbon atoms.

[0041] Examples of the aliphatic dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid.

[0042] The amorphous polyester resin may be used alone or in combination with other amorphous polyester resins.

[0043] ((Other amorphous polyester resins)) The other non-crystalline polyester resin includes, for example, a diol component and a dicarboxylic acid component as a constituent component. The other non-crystalline polyester resin may further include a crosslinking component as a constituent component. Examples of the crosslinking component include aliphatic alcohols having a valence of 3 or more.

[0044] -Diol component- The diol component is not particularly limited and can be appropriately selected depending on the purpose. For example, aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and the like. Examples of the diol include diols having an oxyalkylene group such as polypropylene glycol and polytetramethylene glycol; alicyclic diols such as 1,4-cyclohexanedimethanol and hydrogenated bisphenol A; alicyclic diols to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added; bisphenols such as bisphenol A, bisphenol F, and bisphenol S; and alkylene oxide adducts of bisphenols such as bisphenols to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added. Among these, aliphatic diols having 4 to 12 carbon atoms are preferred. These diols may be used alone or in combination of two or more.

[0045] -Dicarboxylic acid component- The dicarboxylic acid component is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include aliphatic dicarboxylic acids, aromatic dicarboxylic acids, etc. In addition, anhydrides, lower (1 to 3 carbon atoms) alkyl esters, or halides of these may be used.

[0046] The aliphatic dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic dicarboxylic acid include succinic acid, adipic acid, sebacic acid, dodecanedioic acid, maleic acid, and fumaric acid.

[0047] The aromatic dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aromatic dicarboxylic acid include phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. Among these, aliphatic dicarboxylic acids having 4 to 12 carbon atoms are preferred.

[0048] These dicarboxylic acids may be used alone or in combination of two or more.

[0049] -Trivalent or higher aliphatic alcohol- The trihydric or higher aliphatic alcohol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. Among these, trihydric to tetrahydric aliphatic alcohols are preferred. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more.

[0050] The glass transition point (also called glass transition temperature) Tg of polyester resin at the first heating stage in differential scanning calorimetry (DSC) 1st The temperature is preferably 20°C to 50°C.

[0051] In order to improve the low-temperature fixing property of the toner, a method of lowering the glass transition point (also called glass transition temperature) Tg of the crystalline polyester resin or a method of reducing the molecular weight of the crystalline polyester resin can be considered so that the amorphous polyester resin melts together with the crystalline polyester resin. If the melt viscosity of the amorphous polyester resin is reduced by lowering the glass transition point Tg of the amorphous polyester resin or by reducing the molecular weight of the crystalline polyester resin, the heat-resistant storage stability of the toner and the high-temperature offset property during fixing may be deteriorated.

[0052] In this embodiment, the amorphous polyester resin contains a diol component as a constituent component, and the diol component preferably contains 50 mol % or more of an aliphatic diol having 3 to 10 carbon atoms. This can lower the glass transition point Tg and melt viscosity, and ensure low-temperature fixability. In addition, the amorphous polyester resin preferably contains a trivalent or higher aliphatic alcohol as a crosslinking component. This allows the amorphous polyester resin to have a branched structure in the molecular skeleton, and the molecular chain has a three-dimensional network structure, so that the amorphous polyester resin has rubber-like properties of being deformed at low temperatures but not flowing. Therefore, the heat-resistant storage stability and high-temperature offset resistance of the toner can be maintained.

[0053] The other non-crystalline polyester resin preferably has at least one of a urethane bond and a urea bond in terms of better adhesion to recording media such as paper. When the other non-crystalline polyester resin has at least one of a urethane bond and a urea bond, the urethane bond or the urea bond behaves like a pseudo-crosslinking point, the rubber-like properties of the other non-crystalline polyester resin are strengthened, and the heat-resistant storage stability and high-temperature offset resistance of the toner are better.

[0054] -Non-crystalline polyester resin having at least one of a urethane bond and a urea bond- The amorphous polyester resin having at least one of a urethane bond and a urea bond is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a reaction product of an amorphous polyester resin having an active hydrogen group and a polyisocyanate. The reaction product can be used as a reaction precursor (hereinafter, sometimes referred to as a "prepolymer") to be reacted with a curing agent described later.

[0055] --Non-crystalline polyester resin having active hydrogen groups-- Examples of the non-crystalline polyester resin having an active hydrogen group include non-crystalline polyester resin having a hydroxyl group.

[0056] --Polyisocyanate-- The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates.

[0057] Examples of diisocyanates include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, isocyanurates, and those blocked with phenol derivatives, oximes, caprolactams, etc.

[0058] The aliphatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, methyl 2,6-diisocyanatocaproate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, tetradecamethylene diisocyanate, trimethylhexane diisocyanate, and tetramethylhexane diisocyanate.

[0059] The alicyclic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alicyclic diisocyanate include isophorone diisocyanate and cyclohexylmethane diisocyanate.

[0060] The aromatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include tolylene diisocyanate, diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatodiphenyl, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 4,4'-diisocyanato-3-methyldiphenylmethane, 4,4'-diisocyanato-diphenyl ether, etc. The aromatic aliphatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include α,α,α',α'-tetramethylxylylene diisocyanate, etc.

[0061] The isocyanurates are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include tris(isocyanatoalkyl)isocyanurate, tris(isocyanatocycloalkyl)isocyanurate, and the like.

[0062] These polyisocyanates may be used alone or in combination of two or more kinds.

[0063] --Hardening agent-- The curing agent is not particularly limited as long as it reacts with the prepolymer and can be appropriately selected depending on the purpose. For example, an active hydrogen group-containing compound can be used.

[0064] ---Compounds containing active hydrogen groups--- The active hydrogen group in the active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups), amino groups, carboxyl groups, mercapto groups, etc. These may be used alone or in combination of two or more.

[0065] The active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, but amines are preferred because they are capable of forming a urea bond.

[0066] The amines are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include diamines, trivalent or higher amines, amino alcohols, amino mercaptans, amino acids, and blocked amino groups thereof. These may be used alone or in combination of two or more. Among these, diamines and mixtures of diamines and small amounts of trivalent or higher amines are preferred.

[0067] The diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include aromatic diamines, alicyclic diamines, and aliphatic diamines. The aromatic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include phenylenediamine, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. The alicyclic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminocyclohexane, and isophoronediamine. The aliphatic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include ethylenediamine, tetramethylenediamine, and hexamethylenediamine.

[0068] The trivalent or higher amine is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include diethylenetriamine and triethylenetetramine.

[0069] The amino alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino alcohol include ethanolamine and hydroxyethylaniline.

[0070] The amino mercaptan is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino mercaptan include aminoethyl mercaptan and aminopropyl mercaptan.

[0071] The amino acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino acid include aminopropionic acid and aminocaproic acid.

[0072] The blocked amino group is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include ketimine compounds and oxazoline compounds obtained by blocking the amino group with ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0073] The molecular structure of the polyester resin can be confirmed by NMR measurement in solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 and 990±10cm -1 One method is to detect polyester resins that do not have absorption due to olefin δCH (out-of-plane bending vibration).

[0074] The content of the polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50 parts by mass to 90 parts by mass, more preferably 70 parts by mass to 85 parts by mass, relative to 100 parts by mass of the toner. If the content is less than 50 parts by mass, low-temperature fixability and high-temperature offset resistance may deteriorate, and if it exceeds 90 parts by mass, heat-resistant storage stability may deteriorate, and the glossiness and coloring of the image obtained after fixing may decrease. If the content is within the more preferred range, it is advantageous in that all of low-temperature fixability, high-temperature offset resistance, and heat-resistant storage stability are excellent.

[0075] (Other binder resins) The toner according to an embodiment may contain other binder resin components in addition to the polyester resin described above. Examples of other binder resins include known binder resins such as silicone resins, styrene-acrylic resins, styrene resins, acrylic resins, epoxy resins, diene resins, phenol resins, terpene resins, coumarin resins, amide-imide resins, butyral resins, urethane resins, and ethylene-vinyl acetate resins.

[0076] [Organic resin fine particles] The organic resin particles are disposed on the surface of the toner. The organic resin particles are not disposed in a layered state covering the surface of the toner, but are disposed in a scattered state on the surface of the toner.

[0077] The organic resin particles have a core-shell structure consisting of a core having a resin (a) containing a styrene-acrylic resin and not containing a carboxyl group, and a shell having a resin (b) containing a carboxyl group. Note that the organic resin particles do not necessarily have to have a shell, and may be composed of only a core.

[0078] (Resin (a)) The resin (a) is a polymer obtained by homopolymerizing or copolymerizing a vinyl monomer. Examples of the vinyl monomer include the following (1) to (10).

[0079] (1) Vinyl hydrocarbons Examples of the vinyl hydrocarbon include (1-1) aliphatic vinyl hydrocarbons, (1-2) alicyclic vinyl hydrocarbons, and (1-3) aromatic vinyl hydrocarbons.

[0080] (1-1) Aliphatic vinyl hydrocarbons Aliphatic vinyl hydrocarbons include alkenes and alkadienes. Specific examples of alkenes include ethylene, propylene, and α-olefins. Specific examples of alkadienes include butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, and 1,7-octadiene.

[0081] (1-2) Alicyclic vinyl hydrocarbons Alicyclic vinyl hydrocarbons include mono- or di-cycloalkenes and alkadienes, and specific examples include (di)cyclopentadiene, terpene, and the like.

[0082] (1-3) Aromatic vinyl hydrocarbons Examples of aromatic vinyl hydrocarbons include styrene and its hydrocarbyl (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituted derivatives, and specific examples thereof include α-methylstyrene, 2,4-dimethylstyrene and vinylnaphthalene.

[0083] (2) Carboxyl-containing vinyl monomers and their salts Examples of the carboxyl group-containing vinyl monomer and its salt include unsaturated monocarboxylic acids (salts) having 3 to 30 carbon atoms, unsaturated dicarboxylic acids (salts), and their anhydrides (salts), and their monoalkyl (carbon number 1 to 24) esters or salts.

[0084] Specific examples thereof include carboxyl group-containing vinyl monomers such as (meth)acrylic acid, (anhydride) maleic acid, maleic acid monoalkyl esters, fumaric acid, fumaric acid monoalkyl esters, crotonic acid, itaconic acid, itaconic acid monoalkyl esters, itaconic acid glycol monoether, citraconic acid, citraconic acid monoalkyl esters, and cinnamic acid, and metal salts thereof.

[0085] In the present embodiment, the term "(salt)" refers to an acid or a salt thereof. For example, an unsaturated monocarboxylic acid (salt) having 3 to 30 carbon atoms refers to an unsaturated monocarboxylic acid or a salt thereof.

[0086] "(Meth)acrylic" means methacrylic acid or acrylic acid. That is, "(meth)acryloyl" means methacryloyl or acryloyl, and "(meth)acrylate" means methacrylate or acrylate.

[0087] (3) Sulfonic acid-containing vinyl monomers, vinyl sulfate monoesters, and their salts Examples of the sulfonic acid group-containing vinyl monomer, vinyl sulfate monoester, and salts thereof include alkene sulfonic acids (salts) having 2 to 14 carbon atoms, alkyl sulfonic acids (salts) having 2 to 24 carbon atoms, sulfo(hydroxy)alkyl-(meth)acrylates (salts) or (meth)acrylamides (salts), and alkylaryl sulfosuccinic acids (salts). Specifically, examples of the alkene sulfonic acids having 2 to 14 carbon atoms include vinyl sulfonic acid (salts), examples of the alkyl sulfonic acids having 2 to 24 carbon atoms include α-methylstyrene sulfonic acid (salts), and examples of the sulfo(hydroxy)alkyl-(meth)acrylates (salts) or (meth)acrylamides (salts) include sulfopropyl(meth)acrylates (salts), sulfate esters (salts), or sulfonic acid group-containing vinyl monomers (salts).

[0088] (4) Phosphate-containing vinyl monomers and their salts: Examples of the phosphoric acid group-containing vinyl monomer and its salt include (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphoric acid monoester (salt) and (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphonic acid (salt).

[0089] Specific examples of the (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphate monoester (salt) include 2-hydroxyethyl (meth)acryloyl phosphate (salt) and phenyl-2-acryloyloxyethyl phosphate (salt).

[0090] Specific examples of (meth)acryloyloxyalkyl (carbon number: 1 to 24)phosphonic acids (salts) include 2-acryloyloxyethylphosphonic acid (salts).

[0091] Examples of the salts of (2) to (4) above include alkali metal salts (sodium salts, potassium salts, etc.), alkaline earth metal salts (calcium salts, magnesium salts, etc.), ammonium salts, amine salts, and quaternary ammonium salts.

[0092] (5) Hydroxyl-containing vinyl monomers Examples of hydroxyl group-containing vinyl monomers include hydroxystyrene, N-methylol (meth)acrylamide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, (meth)allyl alcohol, crotyl alcohol, isocrotyl alcohol, 1-buten-3-ol, 2-buten-1-ol, 2-butene-1,4-diol, propargyl alcohol, 2-hydroxyethyl propenyl ether, and sucrose allyl ether.

[0093] (6) Nitrogen-containing vinyl monomers Examples of the nitrogen-containing vinyl monomer include an amino group-containing vinyl monomer, an amide group-containing vinyl monomer, a nitrile group-containing vinyl monomer, a quaternary ammonium cation group-containing vinyl monomer, and a nitro group-containing vinyl monomer.

[0094] Examples of the amino group-containing vinyl monomer include aminoethyl (meth)acrylate.

[0095] Examples of the amide group-containing vinyl monomer include (meth)acrylamide and N-methyl(meth)acrylamide.

[0096] Examples of the nitrile group-containing vinyl monomer include (meth)acrylonitrile, cyanostyrene, and cyanoacrylate.

[0097] Examples of the vinyl monomer containing a quaternary ammonium cation group include quaternized products of tertiary amine group-containing vinyl monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and diallylamine (which are quaternized using a quaternizing agent such as methyl chloride, dimethyl sulfate, benzyl chloride, or dimethyl carbonate).

[0098] Nitro group-containing vinyl monomers include nitrostyrene.

[0099] (7) Epoxy group-containing vinyl monomer Examples of the epoxy group-containing vinyl monomer include glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and p-vinylphenyl phenyl oxide.

[0100] (8) Halogen-containing vinyl monomers Examples of halogen-containing vinyl monomers include vinyl chloride, vinyl bromide, vinylidene chloride, allyl chloride, chlorostyrene, bromostyrene, dichlorostyrene, chloromethylstyrene, tetrafluorostyrene, and chloroprene.

[0101] (9) Vinyl ester Examples of vinyl esters include vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinyl benzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl (meth)acrylate, vinyl methoxyacetate, vinyl benzoate, ethyl α-ethoxyacrylate, alkyl (meth)acrylates having an alkyl group having 1 to 50 carbon atoms [methyl (meth)acrylate], ) acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, behenyl (meth)acrylate, etc.)], dialkyl fumarate (wherein the two alkyl groups are linear, branched or alicyclic groups having 2 to 8 carbon atoms), dialkyl Examples of the polyalkylene glycol include maleates (wherein the two alkyl groups are straight-chain, branched-chain or alicyclic groups having 2 to 8 carbon atoms), poly(meth)allyloxyalkanes (diallyloxyethane, triallyloxyethane, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, tetramethallyloxyethane, etc.), vinyl monomers having polyalkylene glycol chains (polyethylene glycol (molecular weight 300) mono(meth)acrylate, polypropylene glycol (molecular weight 500) monoacrylate, methyl alcohol ethylene oxide 10 mol adduct (meth)acrylate, lauryl alcohol ethylene oxide 30 mol adduct (meth)acrylate, etc.), poly(meth)acrylates (poly(meth)acrylates of polyhydric alcohols: ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate, etc.).

[0102] (10) Vinyl (thio) ether An example of the vinyl (thio)ether is vinyl methyl ether.

[0103] (11) Vinyl ketone An example of the vinyl ketone is vinyl methyl ketone.

[0104] (12) Other vinyl monomers Other vinyl monomers include tetrafluoroethylene, fluoroacrylate, isocyanatoethyl (meth)acrylate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate.

[0105] The resin (a) may use one of the vinyl monomers (1) to (12) above either alone or in combination of two or more thereof.

[0106] From the viewpoint of low-temperature fixability of organic resin particles, the resin (a) preferably includes a styrene-(meth)acrylic acid ester copolymer and a (meth)acrylic acid ester copolymer, and more preferably includes a styrene-(meth)acrylic acid ester copolymer.

[0107] (Resin (b)) The resin (b) may be a polymer obtained by homopolymerizing a vinyl monomer having a carboxyl group or copolymerizing it with another monomer. The vinyl monomer may be the same polymer as that used for the resin (a).

[0108] Resin (b) is a resin containing methacrylic acid and / or acrylic acid in a total amount of preferably 10% by mass to 60% by mass, more preferably 30% by mass to 50% by mass, based on the total weight of resin (b).

[0109] As for the resin (b), like the resin (a), from the viewpoint of the low-temperature fixing property of the organic resin fine particles, a styrene-(meth)acrylic acid ester copolymer and a (meth)acrylic acid ester copolymer are preferable, and a styrene-(meth)acrylic acid ester copolymer is more preferable.

[0110] The acid values ​​of the resin (a) and the resin (b) will be explained.

[0111] From the viewpoints of low-temperature fixability and the formation of a core-shell structure, the acid value of the resin (a) is preferably 0 mgKOH / g.

[0112] The acid value of the resin (b) is preferably 75 mgKOH / g to 400 mgKOH / g, and more preferably 150 mgKOH / g to 300 mgKOH / g. If the acid value of the resin (b) is within this range, it is easy to form a structure in which organic resin particles containing the core resin (a) and the shell resin (b) are attached to the surface of the toner.

[0113] ((Acid value measurement)) The acid value was measured under the following conditions according to the measurement method described in JIS K0070-1992. However, when the sample was not soluble, dioxane, tetrahydrofuran, etc. were used as the solvent. Specifically, the acid value is determined by the following procedure. -Measurement conditions- Measurement equipment: Potentiometric automatic titrator (DL-53 Titrator, Mettler Toledo) Electrode used: DG113-SC (Mettler Toledo) Analysis software: LabX Light Version 1.00.000 · Calibration of the instrument: A mixed solvent of 120 ml of toluene and 30 ml of ethanol was used. ·Measurement temperature: 23℃

[0114] The oxidation value can be measured using the above-mentioned measuring device, but specifically, it was calculated as follows: The acid value was calculated by titrating with a previously standardized N / 10 alcohol solution of potassium hydroxide, and the amount of the alcohol solution of potassium hydroxide consumed was calculated as follows: Acid value = KOH (ml) x N x 56.1 / sample weight (N is the factor of N / 10KOH)

[0115] Glass transition temperature Tg of resin (a) and resin (b) at the first heating 1st This article explains:

[0116] Glass transition temperature (Tg) of resin (a) and resin (b) at the first heating time of differential scanning calorimetry (DSC) 1st The glass transition temperature Tg at the first temperature rise is preferably 30° C. to 70° C. 1st If the temperature is less than 30°C, the effect of heat resistance cannot be obtained. 1st If the temperature exceeds 70° C., the low-temperature fixing is significantly hindered.

[0117] In this embodiment, the glass transition temperature Tg 1st Specifically, this is determined by the following procedure: Shimadzu Corporation's TA-60WS and DSC-60 are used as measuring devices, and measurements are performed under the following measuring conditions. (Measurement conditions) Sample container: Aluminum sample pan (with lid) Sample size: 5mg Reference: Aluminum sample pan (10 mg alumina) Atmosphere: Nitrogen (flow rate 50ml / min) ((Temperature conditions)) ·Starting temperature: 20℃ Heating rate: 10℃ / min ·End temperature: 150℃ Hold Time: None ·Cooling temperature: 10℃ / min ·End temperature: 20℃ Hold Time: None Heating rate: 10℃ / min ·End temperature: 150℃

[0118] The measurement results were analyzed using Shimadzu Corporation's data analysis software (TA-60, version 1.52). The analysis method involves specifying a range of ±5°C centered on the point showing the maximum peak on the lowest temperature side of the DrDSC curve, which is the DSC differential curve for the first heating, and determining the peak temperature using the peak analysis function of the analysis software. Next, the maximum endothermic temperature of the DSC curve is determined using the peak analysis function of the analysis software within the range of the peak temperature +5°C and -5°C. The temperature shown here is the glass transition point Tg of the resin of the measurement sample during the first heating. 1st is equivalent to.

[0119] The mass ratio of resin (a) to resin (b) contained in the organic resin fine particles is 5 / 95 to 95 / 5, preferably 25 / 75 to 75 / 25, and more preferably 40 / 60 to 60 / 40. When the mass ratio is 95 / 5 or more, the organic resin fine particles have excellent heat-resistant storage stability. When the mass ratio is 5 / 95 or less, toner particles in which the organic resin fine particles are attached to the surfaces of the toner base particles are easily formed.

[0120] In addition, when the organic resin fine particles preliminarily mixed during emulsification are uniformly adhered to the surfaces of the toner base particles and then the toner base particles are washed with an alkaline aqueous solution, all or a part of the resin (b) in the organic resin fine particles adhered to the surfaces of the toner base particles is removed, thereby making it possible to control the state of the organic resin fine particles on the surfaces of the toner base particles.

[0121] Methods for producing organic resin fine particles containing resin (a) and resin (b) as constituent components include known production methods, such as the following production methods (I) to (V). (I) A method of carrying out seed polymerization of constituent monomers of resin (a) using fine particles of resin (b) in an aqueous dispersion as seeds. (II) A method of seed polymerization of constituent monomers of resin (b) using fine particles of resin (a) in an aqueous dispersion as seeds. (III) A method in which a mixture of resin (a) and resin (b) is emulsified in an aqueous medium to obtain an aqueous dispersion of resin fine particles. (IV) A method in which a mixture of resin (a) and monomers constituting resin (b) is emulsified in an aqueous medium, and then the monomers constituting resin (b) are polymerized to obtain an aqueous dispersion of resin fine particles. (V) A method in which a mixture of constituent monomers of resin (a) and resin (b) is emulsified in an aqueous medium, and then the constituent monomers of resin (a) are polymerized to obtain an aqueous dispersion of resin fine particles.

[0122] In addition, the fact that the organic resin microparticles contain resin (a) and resin (b) as constituent components within the same particle can be confirmed by observing element mapping images of a cut surface of the organic resin microparticles using a known surface elemental analysis device (TOF-SIMS, EDX-SEM, etc.) and by observing electron microscope images of a cut surface of the organic resin microparticles stained with a stain corresponding to the functional groups contained in resin (a1) and resin (a2).

[0123] Specific examples of (I) include the following methods. First, the constituent monomers of resin (b) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing resin (b). Then, the constituent monomers of resin (a) are seed-polymerized using the aqueous dispersion as a seed, or resin (b) previously produced by solution polymerization or the like is emulsified and dispersed in water. Then, the constituent monomers of resin (a) are seed-polymerized using the emulsified dispersion as a seed.

[0124] Specific examples of (II) include the following methods. First, the constituent monomers of the resin (a) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing the resin (a). Then, the constituent monomers of the resin (b) are seed-polymerized using the aqueous dispersion as a seed, and the resin (a) previously produced by solution polymerization or the like is emulsified and dispersed in water. Then, the constituent monomers of the resin (b) are seed-polymerized using the emulsified dispersion as a seed.

[0125] A specific example of (III) is a method in which a solution or melt containing resin (a) and resin (b) which have been produced in advance by solution polymerization or the like is mixed, and then the mixture is emulsified and dispersed in an aqueous medium.

[0126] A specific example of (IV) is a method in which resin (a), which has been produced in advance by solution polymerization or the like, is mixed with constituent monomers of resin (b), the mixture obtained is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (b) are polymerized in the emulsion dispersion to produce resin (b).

[0127] A specific example of (V) is a method in which the constituent monomers of (a) are mixed with (b) which has been produced in advance by solution polymerization or the like, the mixture obtained is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (a) are polymerized in the emulsion dispersion to produce resin (a).

[0128] Any of the production methods (I) to (V) is suitable.

[0129] The organic resin particles are preferably used as an aqueous dispersion, and the aqueous medium of the dispersion can be any liquid containing water as an essential component without any particular limitations. In this embodiment, since the organic resin particles and the surfactant are provided on the surface of the toner, it is preferable to use, for example, an aqueous solution containing a surfactant in water as the aqueous medium.

[0130] The particle diameter of the organic resin fine particles is preferably 10 nm to 100 nm. If the particle diameter is less than 10 nm, the coverage rate on the toner surface increases, and low-temperature fixing performance may decrease. If the particle diameter exceeds 100 nm, the voids on the toner surface become large, and the effect of heat-resistant storage performance decreases.

[0131] The particle size of the organic resin fine particles can be measured by using a laser Doppler particle size distribution measuring device, by adding a sample to be measured to the measuring device using a dropper or syringe, etc. The measurement conditions are as follows. (Measurement conditions) Equipment: nanotrac UPA-150EX (manufactured by Nikkiso Co., Ltd.) Distribution display: Volume Number of channels: 52 ·Measurement time: 30sec Particle refractive index: 1.81 ·Temperature: 25℃ ·Particle shape: spherical ·Viscosity (CP): High temperature viscosity 0.797 Low temperature viscosity 1.002 Solvent refractive index: 1.333 Solvent: Water

[0132] The content of the organic resin particles A in the toner is preferably 0.2% by mass to 5% by mass. If the content is less than 0.2% by mass, the heat-resistant storage effect is not sufficiently obtained. If the content is more than 5%, the low-temperature fixation is significantly hindered.

[0133] The content of the organic resin particles A in the toner can be measured by a pyrolysis gas chromatograph as follows. (Measurement conditions) Gas chromatograph: 7890B (Agilent Technologies) Pyrolysis equipment: EGA / PY-3030D (manufactured by Frontier Labs) ·Pyrolysis condition temperature: 600℃ Interface temperature: 400℃ Detector temperature: 320℃ Oven temperature: 50℃(10min)-<10℃ / min>-150℃(0min)-<20℃ / min>-320℃(3.5min) Column: UA5-30M-1F (30m x 0.25mm i.d., 1.0μm film) Detector: FID

[0134] [Anionic surfactants] The anionic surfactant is present by bonding to the surface of the toner and contains a carboxyl group.

[0135] Examples of the anionic surfactant include ether carboxylic acids or salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, sulfate esters or ether sulfate esters and salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, sulfonates having a hydrocarbon group having 8 to 24 carbon atoms, sulfosuccinates having one or two hydrocarbon groups having 8 to 24 carbon atoms, phosphate esters or ether phosphate esters and salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, fatty acid salts having a hydrocarbon group having 8 to 24 carbon atoms, and acylated amino acid salts having a hydrocarbon group having 8 to 24 carbon atoms.

[0136] Examples of the ether carboxylic acid or a salt thereof having a hydrocarbon group having 8 to 24 carbon atoms include sodium lauryl ether acetate and (poly)oxyethylene (number of moles added: 1 to 100) sodium lauryl ether acetate.

[0137] Examples of sulfates or ether sulfates having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) triethanolamine lauryl sulfate, and (poly)oxyethylene (number of moles added: 1 to 100) sodium coconut oil fatty acid monoethanolamide sulfate.

[0138] Examples of sulfonates having a hydrocarbon group having 8 to 24 carbon atoms include sodium dodecylbenzenesulfonate.

[0139] Examples of the phosphate ester or ether phosphate ester having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl phosphate and sodium (poly)oxyethylene (addition mole number 1 to 100) lauryl ether phosphate.

[0140] Examples of the fatty acid salt having a hydrocarbon group having 8 to 24 carbon atoms include sodium laurate and triethanolamine laurate.

[0141] Examples of the acylated amino acid salts having a hydrocarbon group having 8 to 24 carbon atoms include sodium methyl coconut taurate, sodium coconut sarcosine, triethanolamine coconut sarcosine, N-triethanolamine coconut acyl-L-glutamate, sodium N-sodium coconut acyl-L-glutamate, and sodium lauroylmethyl-β-alanine.

[0142] If necessary, the solution may further contain a buffering agent such as sodium acetate, sodium citrate, sodium bicarbonate, etc. These may be used alone or in combination of two or more kinds.

[0143] If necessary, the composition may further contain, as a protective colloid, a water-soluble cellulose compound, an alkali metal salt of polymethacrylic acid, etc. These may be used alone or in combination of two or more kinds.

[0144] The acid value of the anionic surfactant is preferably 100 mgKOH / g to 200 mgKOH / g, more preferably 110 mgKOH / g to 180 mgKOH / g, and even more preferably 130 mgKOH / g to 160 mgKOH / g. If the acid value of the anionic surfactant is 100 mgKOH / g to 200 mgKOH / g, it is less susceptible to the influence of moisture in the atmosphere, and a good negative charge effect can be obtained.

[0145] Specifically, it is preferable to use succinic acid derivatives such as sulfosuccinic acid ester salts as the anionic surfactant having a carboxyl group.

[0146] Anionic surfactants having a carboxyl group include commercially available sulfosuccinate salt surfactants such as Viewlite SSS (manufactured by Sanyo Chemical Industries, Ltd.), Carabon DA-72 (manufactured by Sanyo Chemical Industries, Ltd.), and Pelex OT-P (manufactured by Kao Corporation). In addition, they can be obtained by hydrolyzing the ester group of a sulfosuccinate salt surfactant with an acid.

[0147] For example, the desired sulfosuccinate salt can be obtained by esterifying maleic acid with an alkyl alcohol and sulfonating it with a metal hydrogen sulfite. In this synthesis method, the number of carbon atoms in the alkyl chain of the alkyl alcohol can be freely changed to obtain a sulfosuccinate salt having a desired alkyl chain.

[0148] The presence of these surfactants in the toner can be confirmed by liquid chromatography and an MS detector. For example, the measurement can be performed by the following method using a liquid chromatography system (AQUITY-UPLC / SQD system, manufactured by Nihon Waters).

[0149] Approximately 0.2 g of the toner sample is weighed and placed in 20 mL of methanol and stirred to disperse. After that, ultrasonic waves are applied for 30 minutes and the mixture is left to stand for 24 hours. The supernatant is filtered through a membrane filter with a pore size of 0.2 μm, and the obtained sample is diluted 100 times with methanol and then subjected to the liquid chromatography. The presence of a peak derived from the carboxyl group is confirmed using an MS detector.

[0150] The acid value of the surfactant having a carboxyl group is preferably 100 mgKOH / g to 200 mgKOH / g, in which range the surfactant is less susceptible to the effects of moisture in the atmosphere and provides the best negative chargeability.

[0151] The acid value of a surfactant having a carboxyl group can be measured by the following method using an automatic potentiometric titrator (DL-53 Titrator, Mettler Toledo).

[0152] Titrate with a previously standardized N / 10 caustic potash-alcohol solution, and calculate the acid value using the following formula based on the amount of alcoholic potash solution consumed. Acid value = KOH (ml) x N x 56.1 / sample weight (N is the factor of N / 10KOH)

[0153] [Other surfactants] The toner according to an embodiment may contain other surfactants in addition to the anionic surfactant. Examples of the other surfactants include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, and other emulsifying dispersants.

[0154] Examples of the nonionic surfactant include AO addition type nonionic surfactants and polyhydric alcohol type nonionic surfactants.

[0155] Examples of AO-addition type nonionic surfactants include EO adducts of aliphatic alcohols having 10 to 20 carbon atoms, EO adducts of phenols, EO adducts of nonylphenols, EO adducts of alkylamines having 8 to 22 carbon atoms, and EO adducts of poly(oxypropylene) glycols.

[0156] Examples of polyhydric alcohol-type nonionic surfactants include fatty acid (carbon number 8 to 24) esters of polyhydric (tri- to octahydric or higher) alcohols (carbon number 2 to 30) (e.g., glycerin monostearate, glycerin monooleate, sorbitan monolaurate, sorbitan monooleate, etc.) and alkyl (carbon number 4 to 24) poly(degree of polymerization 1 to 10) glycosides.

[0157] Cationic surfactants include quaternary ammonium salts and amine salts. Specifically, quaternary ammonium salts include stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, and lanolin fatty acid aminopropyl ethyl dimethyl ammonium ethyl sulfate. Examples of the amine salt type include stearic acid diethylaminoethylamide lactate, dilaurylamine hydrochloride, and oleylamine lactate.

[0158] Examples of the amphoteric surfactant include betaine type amphoteric surfactants and amino acid type amphoteric surfactants.

[0159] Examples of the betaine type amphoteric surfactant include coconut oil fatty acid amidopropyl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl hydroxysulfobetaine.

[0160] Examples of the amino acid type amphoteric surfactant include sodium β-laurylaminopropionate.

[0161] Other emulsifying dispersants include, for example, reactive activators [which are not particularly limited as long as they have radical reactivity, and specifically include ADEKA REASOAP {registered trademark, manufactured by ADEKA Corporation} SE-10N, SR-10, SR-20, SR-30, ER-20, ER-30, AQUALON {registered trademark, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.} HS-10, KH-05, KH-10, KH-1025, ELEMINOL {registered trademark, manufactured by Sanyo Chemical Industries, Ltd.} JS-20, LATEMUL {registered trademark, manufactured by Kao Corporation} PD-104, PD-420, PD-430. , IONET {registered trademark, MO-200, manufactured by Sanyo Chemical Industries, Ltd.}, polyvinyl alcohol, starch and derivatives thereof, cellulose derivatives such as carboxymethyl cellulose, methyl cellulose, and hydroxyethyl cellulose, carboxyl group-containing (co)polymers such as polysodium acrylate, and emulsifying dispersants having urethane groups or ester groups described in U.S. Pat. No. 5,906,704 (for example, polycaprolactone polyol and polyether diol linked with polyisocyanate).

[0162] In this embodiment, as the surfactant, from the viewpoint of stabilizing the oil droplets during emulsification and dispersion and sharpening the particle size distribution while obtaining the desired shape, it is preferable to use an anionic surfactant in combination with at least one of a nonionic surfactant and other emulsifying dispersants, and it is more preferable to use an anionic surfactant in combination with other emulsifying dispersants.

[0163] [Other resin components] The organic resin fine particles may contain other resin components in addition to the resin (a) and the resin (b), such as an initiator (and its residue), a chain transfer agent, an antioxidant, a plasticizer, a preservative, a reducing agent, and an organic solvent.

[0164] Examples of other resin components include vinyl resins other than those used in resin (a) and resin (b), polyurethane resins, epoxy resins, polyester resins, polyamide resins, polyimide resins, silicon resins, phenolic resins, melamine resins, urea resins, aniline resins, ionomer resins, and polycarbonate resins.

[0165] Examples of the initiator (and its residue) include known radical polymerization initiators, etc. Specific examples include persulfate initiators such as potassium persulfate and ammonium persulfate, azo initiators such as azobisisobutyronitrile, organic peroxides such as benzoyl peroxide, cumene hydroperoxide, tertiary butyl hydroperoxide, tertiary butyl peroxyisopropyl monocarbonate and tertiary butyl peroxybenzoate, and hydrogen peroxide.

[0166] Examples of the chain transfer agent include n-dodecyl mercaptan, tert-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl thioglycolate, 2-mercaptoethanol, β-mercaptopropionic acid, and α-methylstyrene dimer.

[0167] Examples of the antioxidant include phenol compounds, paraphenylenediamine, hydroquinone, organic sulfur compounds, and organic phosphorus compounds.

[0168] The phenolic compounds include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2′-methylene-bis-(4-methyl-6-t-butylphenol), 2,2′-methylene-bis-(4-ethyl-6-t-butylphenol), 4,4′-thiobis-(3-methyl-6-t-butylphenol), 4,4′-butylidenebis-(3-methyl-6-t-butylphenol), and 4,4′-butylidenebis-(3-methyl-6-t-butylphenol). -6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, and tocopherol.

[0169] Examples of paraphenylenediamines include N-phenyl-N'-isopropyl-p-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, N-phenyl-N-sec-butyl-p-phenylenediamine, N,N'-di-isopropyl-p-phenylenediamine, and N,N'-dimethyl-N,N'-di-t-butyl-p-phenylenediamine.

[0170] Examples of hydroquinone include 2,5-di-t-octylhydroquinone, 2,6-didodecylhydroquinone, 2-dodecylhydroquinone, 2-dodecyl-5-chlorohydroquinone, 2-t-octyl-5-methylhydroquinone, and 2-(2-octadecenyl)-5-methylhydroquinone.

[0171] Examples of the organic sulfur compounds include dilauryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, and ditetradecyl-3,3'-thiodipropionate.

[0172] Examples of the organic phosphorus compound include triphenylphosphine, tri(nonylphenyl)phosphine, tri(dinonylphenyl)phosphine, tricresylphosphine, and tri(2,4-dibutylphenoxy)phosphine.

[0173] Examples of the plasticizer include phthalate esters, aliphatic dibasic acid esters, trimellitate esters, phosphate esters, and fatty acid esters. Specifically, examples of phthalate esters include dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and diisodecyl phthalate. Examples of the aliphatic dibasic acid ester include di-2-ethylhexyl adipate and 2-ethylhexyl sebacate. Examples of trimellitic acid esters include tri-2-ethylhexyl trimellitate and trioctyl trimellitate. Examples of the phosphate ester include triethyl phosphate, tri-2-ethylhexyl phosphate, and tricresyl phosphate. The fatty acid ester may, for example, be butyl oleate.

[0174] Examples of the preservatives include organic nitrogen sulfur compound preservatives and organic sulfur halide preservatives.

[0175] Examples of reducing agents include reducing organic compounds such as ascorbic acid, tartaric acid, citric acid, glucose, and metal formaldehyde sulfoxylates, and reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, and sodium metabisulfite.

[0176] Examples of the organic solvent include ketone solvents [e.g., acetone and methyl ethyl ketone (hereinafter, abbreviated as MEK)], ester solvents (e.g., ethyl acetate and γ-butyrolactone), ether solvents (e.g., THF), amide solvents (e.g., N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and N-methylcaprolactam), alcohol solvents (e.g., isopropyl alcohol), and aromatic hydrocarbon solvents (e.g., toluene and xylene).

[0177] [Other ingredients] The toner according to an embodiment may contain other components, such as a release agent, a colorant, a charge control agent, an external additive, a flowability improver, a cleaning property improver, and a magnetic material.

[0178] (Release agent) The release agent is not particularly limited and can be appropriately selected from known ones.

[0179] Examples of wax and wax release agents include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusin; and petroleum waxes such as paraffin, microcrystalline, and petrolatum.

[0180] In addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax, polyethylene, and polypropylene; synthetic waxes such as esters, ketones, and ethers; and the like.

[0181] Further, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains may be used.

[0182] Among these, hydrocarbon waxes such as paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, and polypropylene wax are preferred.

[0183] The melting point of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. or more and 80° C. or less. If the melting point is less than 60° C., the release agent is likely to melt at low temperatures, and the heat resistance storage stability may be poor. If the melting point is more than 80° C., even if the resin melts and is in the fixing temperature range, the release agent may not melt sufficiently, causing fixing offset and image defects.

[0184] The content of the release agent is not particularly limited and can be appropriately selected according to the purpose, but is preferably 2 to 10 parts by mass, more preferably 3 to 8 parts by mass, relative to 100 parts by mass of the toner. If the content is less than 2 parts by mass, the high-temperature offset resistance and low-temperature fixability during fixing may be poor, and if it exceeds 10 parts by mass, the heat-resistant storage stability may be reduced and image fogging may easily occur. If the content is within the above-mentioned more preferred range, it is advantageous in terms of improving image quality and fixing stability.

[0185] (Coloring agent) The colorant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the colorant include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, and anthrazan yellow BGL. , Isoindolinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Kanmin BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Examples of such pigments include malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, and lithopone.

[0186] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 to 15 parts by mass, and more preferably 3 to 10 parts by mass, per 100 parts by mass of the toner.

[0187] The colorant can also be used as a masterbatch composited with a resin. Examples of resins to be produced by the masterbatch or kneaded with the masterbatch include, in addition to polyester resins, styrene or its substituted polymers such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, Styrene-based copolymers such as styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax. These may be used alone or in combination of two or more.

[0188] The master batch can be obtained by mixing and kneading the resin for the master batch and the colorant under high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin. In addition, a method called the flushing method, in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin and the organic solvent, the colorant is transferred to the resin side, and the water and organic solvent components are removed, is also preferably used because the wet cake of the colorant can be used as it is and does not need to be dried. A high shear dispersing device such as a three-roll mill is preferably used for mixing and kneading.

[0189] (Charge control agent) The charge control agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.

[0190] Specific examples include the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, and the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (both manufactured by Hodogaya Chemical Co., Ltd.), LRA-901, the boron complex LR-147 (manufactured by Nippon Carlit Co., Ltd.), copper phthalocyanine, perylene, quinacridone, azo pigments, and other polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts.

[0191] The content of the charge control agent is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the toner. If the content exceeds 10 parts by mass, the chargeability of the toner is too high, the effect of the main charge control agent is reduced, and the electrostatic attraction force with the developing roller increases, which may lead to a decrease in the fluidity of the developer and a decrease in image density. These charge control agents can be melt-kneaded together with the master batch and resin and then dissolved and dispersed, or of course they can be added when directly dissolved and dispersed in an organic solvent, or they can be fixed on the toner surface after the toner particles are produced.

[0192] (External additives) As the external additive, inorganic fine particles and hydrophobized inorganic fine particles can be used in combination with the oxide fine particles. The average particle size of the hydrophobized primary particles is preferably 1 nm to 100 nm, and inorganic fine particles of 5 nm to 70 nm are more preferable.

[0193] It is also preferred that the hydrophobized inorganic particles contain at least one type of inorganic particles having an average primary particle size of 20 nm or less, and at least one type of inorganic particles having an average primary particle size of 30 nm or more. 2 / g~500m 2 It is preferred that the molecular weight is / g.

[0194] The external additive is not particularly limited and can be appropriately selected depending on the purpose. Examples of the external additive include silica fine particles, hydrophobic silica, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.), metal oxides (e.g., titania, alumina, tin oxide, antimony oxide, etc.), fluoropolymers, etc.

[0195] Suitable additives include hydrophobized silica, titania, titanium oxide, and alumina fine particles. Examples of silica fine particles include R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.). Examples of titania fine particles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, and STT-65C-S (all manufactured by Titanium Industries Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Industries Co., Ltd.), MT-150W, MT-500B, MT-600B, and MT-150A (all manufactured by Teika Co., Ltd.).

[0196] Examples of hydrophobically treated titanium oxide particles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Corporation), and IT-S (manufactured by Ishihara Sangyo Kaisha, Ltd.).

[0197] Hydrophobized oxide fine particles, hydrophobized silica fine particles, hydrophobized titania fine particles, and hydrophobized alumina fine particles can be obtained, for example, by treating hydrophilic fine particles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, octyltrimethoxysilane, etc. Silicone oil-treated oxide fine particles and inorganic fine particles, which are treated with silicone oil by heating if necessary, are also suitable.

[0198] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methylhydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacryl-modified silicone oil, and α-methylstyrene-modified silicone oil.

[0199] Examples of inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium dioxide are particularly preferred.

[0200] The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 to 5 parts by mass, and more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the toner.

[0201] The average particle size of the primary particles of the inorganic fine particles is not particularly limited and can be appropriately selected according to the purpose, but is preferably 100 nm or less, more preferably 3 nm to 70 nm. If it is smaller than this range, the inorganic fine particles are buried in the toner and their function is not effectively exerted. If it is larger than this range, the photoconductor surface is damaged unevenly, which is not preferable.

[0202] (Flow improver) The flowability improver is not particularly limited as long as it is capable of performing a surface treatment to increase hydrophobicity and prevent deterioration of flowability and charging properties even under high humidity, and can be appropriately selected according to the purpose, and examples thereof include silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, modified silicone oils, etc. It is particularly preferable that the silica and titanium oxide are surface-treated with such a flowability improver and used as hydrophobic silica and hydrophobic titanium oxide.

[0203] (Cleaning improver) The cleaning property improver is not particularly limited as long as it is added to the toner to remove the developer remaining on the photoconductor or primary transfer medium after transfer, and can be appropriately selected depending on the purpose, and examples thereof include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles. The polymer fine particles preferably have a relatively narrow particle size distribution, and are preferably ones having a volume average particle size of 0.01 μm to 1 μm.

[0204] (Magnetic material) The magnetic material is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include iron powder, magnetite, ferrite, etc. Among these, a white material is preferable in terms of color tone.

[0205] <Characteristics of toner> [Glass transition temperature Tg 1st ] The toner according to one embodiment has a glass transition temperature Tg 1st The temperature is preferably 20°C to 50°C, and more preferably 25°C to 50°C.

[0206] For conventional toners, when the glass transition temperature Tg is about 50° C. or lower, the toner is likely to aggregate due to temperature changes during transportation and storage in summer and tropical regions. As a result, the toner solidifies in the toner bottle and adheres to the developing machine. In addition, toner clogging in the toner bottle can cause poor replenishment, and toner adherence in the developing machine can cause image abnormalities.

[0207] The toner according to the embodiment has a lower glass transition temperature Tg than conventional toners. However, since the polyester resin, which is a low Tg component in the toner, is non-linear, the toner according to the embodiment can maintain heat-resistant storage stability. In particular, when the polyester resin has a urethane bond or urea bond with high cohesive force, the effect of maintaining heat-resistant storage stability becomes more pronounced.

[0208] The toner according to one embodiment has a glass transition temperature Tg 2nd The temperature (also referred to as the glass transition temperature) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 0°C to 30°C, and more preferably from 10°C to 30°C.

[0209] The glass transition temperature Tg of the toner according to an embodiment of the present invention is measured by differential scanning calorimetry (DSC) 1st and the second glass transition temperature Tg 2nd Difference from (Tg 1st -Tg 2nd ) is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the temperature is higher than 0°C (i.e., Tg 1st >Tg 2nd ), and more preferably 10° C. or more. The upper limit of the difference is not particularly limited and can be appropriately selected depending on the purpose. 1st -Tg 2nd ) is preferably 50°C or lower.

[0210] When the toner according to one embodiment contains a crystalline polyester resin, the crystalline polyester resin and the non-crystalline polyester resin, which exist in an incompatible state before heating (before the first temperature increase), become compatible after heating (after the first temperature increase).

[0211] Glass transition temperature (Tg) at first heating 1st If the temperature is less than 20° C., the heat resistance storage stability decreases, blocking in the developing machine, and filming on the photoconductor tends to occur. 1st If the temperature exceeds 50° C., the low-temperature fixing property of the toner decreases.

[0212] Glass transition temperature (Tg) after second heating 2nd If the temperature is less than 0°C, the blocking resistance of the fixed image (printed matter) may decrease. 2nd If the temperature exceeds 30° C., sufficient low-temperature fixability and glossiness may not be obtained.

[0213] [Volume average particle size] The volume average particle diameter of the toner according to the embodiment is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 3 μm to 7 μm. The ratio of the volume average particle diameter to the number average particle diameter is preferably 1.2 or less. It is also preferable that the toner contains components having a volume average particle diameter of 2 μm or less in an amount of 1 number % to 10 number %.

[0214] <Calculation method for various characteristics of toner components> The glass transition point Tg and melting point of the polyester resin may be measured for each of them. Alternatively, the glass transition point Tg, melting point, and mass ratio of the components may be calculated by separating the components contained in the toner from an actual toner by GPC or the like and measuring the separated components using the analytical method described below.

[0215] Separation of each component by GPC can be carried out, for example, by the following method.

[0216] First, in a GPC measurement using THF (tetrahydrofuran) as the mobile phase, the eluate is fractionated using a fraction collector or the like, and fractions corresponding to a desired molecular weight portion within the full integral of the elution curve are collected.

[0217] The combined eluate is concentrated and dried using an evaporator or the like, and the solid content is dissolved in a heavy solvent such as deuterated chloroform or deuterated THF, 1 H-NMR measurement is performed, and the ratio of constituent monomers can be calculated from the integral ratio of each element.

[0218] As another method, the eluate is concentrated, then hydrolyzed with sodium hydroxide or the like, and the decomposition products are subjected to qualitative and quantitative analysis by high performance liquid chromatography (HPLC) or the like, whereby the ratio of the constituent monomers can be calculated.

[0219] In addition, when the toner forms toner base particles while generating a non-crystalline polyester resin by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, the non-crystalline polyester resin may be separated from the actual toner by GPC or the like to determine the glass transition point Tg of the non-crystalline polyester resin. Alternatively, the non-crystalline polyester resin may be synthesized by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, and the glass transition point Tg of the synthesized non-crystalline polyester resin may be measured.

[0220] [Means for separating toner components] An example of a method for separating each component when analyzing a toner is described in detail. First, 1 g of toner is put into 100 mL of THF, and the solution is obtained by dissolving the soluble portion while stirring for 30 minutes under the condition of 25°C. The solution is filtered through a membrane filter with an opening of 0.2 μm to obtain the THF-soluble portion in the toner. Next, the THF-soluble portion is dissolved in THF to prepare a sample for GPC measurement, and is injected into the GPC used to measure the molecular weight of each resin described above. Meanwhile, a fraction collector is placed at the eluate outlet of the GPC, and the eluate is fractionated at a predetermined count, and the eluate is obtained at 5% area ratios from the start of elution of the elution curve (the rise of the curve). Next, for each elution portion, 30 mg of a sample is dissolved in 1 mL of deuterated chloroform, and 0.05 vol% of tetramethylsilane (TMS) is added as a reference substance. The solution is filled into a 5 mm diameter glass tube for NMR measurement, and a spectrum is obtained by integrating 128 times at a temperature of 23° C. to 25° C. using a nuclear magnetic resonance apparatus (JNM-AL400 manufactured by JEOL Ltd.). The monomer composition and composition ratio of the crystalline polyester resin and non-crystalline polyester resin contained in the toner can be determined from the peak integral ratio of the obtained spectrum.

[0221] For example, the components originating from the peaks can be identified from the peak positions, and the component ratios of the constituent monomers can be calculated from the respective integral ratios, as described below. Peak at around 8.25 ppm: Benzene ring of trimellitic acid (one hydrogen) Peaks around 8.07 ppm to 8.10 ppm: benzene ring of terephthalic acid (4 hydrogen atoms) Peaks around 7.1 ppm to 7.25 ppm: Benzene ring of bisphenol A (4 hydrogen atoms) Peaks around 6.8 ppm: Benzene ring of bisphenol A (4 hydrogens) and double bond of fumaric acid (2 hydrogens) Peaks around 5.2 ppm to 5.4 ppm: Methine derivatives of bisphenol A propylene oxide adducts (one hydrogen atom) Peaks around 4.0 ppm to 5.0 ppm: derived from methylene of aliphatic alcohol (2 hydrogen atoms) Peaks around 3.7 ppm to 4.7 ppm: methylene-derived compounds of bisphenol A propylene oxide adducts (two hydrogen atoms) and methylene-derived compounds of bisphenol A ethylene oxide adducts (four hydrogen atoms) Peaks around 2.2 ppm to 2.6 ppm: derived from methylene of aliphatic dicarboxylic acid (2 hydrogens) Peaks around 1.6 ppm: Bisphenol A and methyl groups of aliphatic alcohols (6 hydrogen atoms)

[0222] From these results, for example, the extract recovered in a fraction containing 90% or more of crystalline polyester resin can be treated as a crystalline polyester resin, and similarly, the extract recovered in a fraction containing 90% or more of amorphous polyester resin can be treated as an amorphous polyester resin.

[0223] [Measuring method for melting point and glass transition point Tg] The melting point and glass transition point Tg can be measured, for example, using a DSC system (differential scanning calorimeter) ("Q-200", manufactured by TA Instruments). Specifically, the melting point and glass transition point of the target sample can be measured by the following procedure.

[0224] First, about 5.0 mg of the target sample is placed in an aluminum sample container, the sample container is placed on a holder unit, and set in an electric furnace. Next, in a nitrogen atmosphere, the sample is heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample is cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). During each of the first and second heating, a DSC curve is measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments).

[0225] From the obtained DSC curves, the DSC curve at the first temperature rise can be selected using the analysis program in the Q-200 system to determine the glass transition point of the target sample at the first temperature rise. Similarly, the DSC curve at the second temperature rise can be selected to determine the glass transition point of the target sample at the second temperature rise.

[0226] Furthermore, from the obtained DSC curves, the analysis program in the Q-200 system can be used to select the DSC curve during the first heating and determine the endothermic peak top temperature during the first heating of the target sample as the melting point. Similarly, the DSC curve during the second heating can be selected and the endothermic peak top temperature during the second heating of the target sample as the melting point.

[0227] When toner was used as the target sample, the glass transition temperature during the first heating was measured as Tg 1st The glass transition temperature during the second heating is Tg 2nd Let us assume that.

[0228] In addition, unless otherwise specified, the melting point and glass transition point Tg of the constituent components of the toner such as polyester resin are the endothermic peak top temperature and glass transition point Tg of each sample during the second heating.

[0229] As described above, the toner according to one embodiment has organic resin particles having a core-shell structure composed of a core having a resin (a) that contains a styrene acrylic resin and does not contain a carboxyl group and a shell having a resin (b) that contains a carboxyl group, and an anionic surfactant that contains a carboxyl group, on the surface of the toner base particle.

[0230] Since the shell of the organic resin fine particles is formed by containing the resin (b) containing a carboxyl group, when the toner is washed with an organic solvent during the production of the toner, at least a part of the shell dissolves, and a part of the organic resin fine particles attached to the toner base particles can be detached. In addition, since the core is formed by containing the resin (a) containing a styrene acrylic resin and not containing a carboxyl group, it is difficult to dissolve in the organic solvent even when the toner is washed with an organic solvent, and can remain on the surface of the toner base particles. Therefore, the organic resin fine particles composed of the core can be present scattered on the surface of the toner base particles, so that the low-temperature fixability of the toner can be suppressed from being hindered, and the heat resistance can be improved.

[0231] In addition, the anionic surfactant can enhance the dispersibility of the toner base particles in the toner by adhering to the surface of the toner base particles. In addition, the carboxyl group contained in the anionic surfactant has the effect of imparting negative chargeability and can suppress charging inhibition. Therefore, by including an anionic surfactant containing a carboxyl group, the toner can impart good dispersibility and excellent negative chargeability to the toner base particles.

[0232] Therefore, the toner according to one embodiment has organic resin fine particles having the above-mentioned core-shell structure and an anionic surfactant containing a carboxyl group on the surface of the toner base particles, and thus can have excellent low-temperature fixing properties, high-temperature offset resistance, heat-resistant storage stability and chargeability.

[0233] The toner according to one embodiment has a glass transition point Tg 1st can be set to 30° C. to 70° C. This allows the toner to maintain its low-temperature fixability and heat-resistant storage stability, thereby reducing the occurrence of blocking in a developing machine and filming on a photoconductor.

[0234] The toner according to the embodiment can have a particle diameter of the organic resin fine particles of 10 nm to 100 nm. This allows the coverage rate of the toner base particle surface to be optimized, and prevents the coverage rate of the toner surface from becoming too high, while suppressing the size of the voids on the surface of the toner base particle. Therefore, the toner according to the embodiment can maintain good low-temperature fixing performance and heat-resistant storage performance.

[0235] The toner according to an embodiment can have an organic resin fine particle content of 0.2% by mass to 5% by mass relative to the toner. This provides sufficient heat-resistant storage effect and prevents the increase of inhibition of low-temperature fixation. Therefore, the toner according to an embodiment can maintain low-temperature fixability and heat-resistant storage ability well.

[0236] In the toner according to an embodiment, the acid value of the anionic surfactant can be set to 100 mgKOH / g to 200 mgKOH / g, which makes the toner base particles less susceptible to the effects of moisture in the air and improves the effect of negative chargeability, thereby enabling the chargeability of the toner to be maintained at a good level.

[0237] The toner according to an embodiment can use a succinic acid derivative as an anionic surfactant. The number of carbon atoms in the alkyl chain of the succinic acid derivative can be freely changed, and a succinic acid derivative having a desired alkyl chain can be obtained, so that the chargeability of the toner can be further improved.

[0238] <Toner manufacturing method> The method for producing the toner according to one embodiment can be appropriately selected depending on the purpose, but preferably includes a granulation step in which an oil phase containing a polyester resin, preferably the crystalline polyester resin, and further containing a release agent, etc., as necessary, is dispersed in an aqueous medium containing organic resin fine particles and an anionic surfactant containing a carboxyl group, thereby granulating toner base particles and adhering the organic resin fine particles and the anionic surfactant containing a carboxyl group to the surfaces of the toner base particles.

[0239] In addition, in the toner manufacturing method according to one embodiment, in the granulation step, the polyester resin contains a non-crystalline polyester resin which is a prepolymer having at least one of a urethane bond and a urea bond, and a non-crystalline polyester resin which does not have a urethane bond or a urea bond, and preferably a crystalline polyester resin, and more preferably uses an oil phase which contains a curing agent or the like as necessary.

[0240] The toner can be produced by a solution suspension method. For example, a method of producing toner base particles can be used in which an amorphous polyester resin is elongated by an elongation reaction and / or a crosslinking reaction between a prepolymer and a curing agent.

[0241] The method for producing toner base particles using this solution suspension method includes a step of preparing an aqueous medium (aqueous medium preparation step), a step of preparing an oil phase containing the toner materials (oil phase preparation step), a step of emulsifying or dispersing the toner materials (emulsifying or dispersing step), and a step of removing the organic solvent (organic solvent removal step).

[0242] (Preparation of aqueous medium) The aqueous medium (aqueous phase) can be prepared, for example, by dispersing resin particles, organic resin fine particles, and an anionic surfactant containing a carboxyl group in the aqueous medium. The amount of resin particles added to the aqueous medium is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.5 parts by mass to 10 parts by mass with respect to 100 parts by mass of the aqueous medium.

[0243] The aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include water, a solvent miscible with water, and a mixture thereof. These may be used alone or in combination of two or more. Among these, water is preferred.

[0244] The solvent miscible with water can be appropriately selected depending on the purpose, and examples thereof include alcohol, lower ketones, dimethylformamide, tetrahydrofuran, cellosolves, etc. The alcohol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include methanol, isopropanol, ethylene glycol, etc. The lower ketones can be appropriately selected depending on the purpose, and examples thereof include acetone, methyl ethyl ketone, etc.

[0245] (Oil phase preparation process) The oil phase containing the toner materials includes at least a crystalline polyester resin, a non-crystalline polyester resin which is a prepolymer having at least one of a urethane bond and a urea bond, and a non-crystalline polyester resin which does not have a urethane bond or a urea bond, and further includes a curing agent, a releasing agent, a colorant, etc., as necessary, and can be prepared by dissolving or dispersing the toner materials in an organic solvent.

[0246] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but an organic solvent having a boiling point of less than 150° C. is preferred in terms of ease of removal.

[0247] The organic solvent having a boiling point of less than 150° C. is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, etc. These may be used alone or in combination of two or more.

[0248] Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, carbon tetrachloride, etc. are preferable, and ethyl acetate is more preferable.

[0249] (Emulsification or dispersion process) The toner materials can be emulsified or dispersed by dispersing the oil phase containing the toner materials in an aqueous medium. At this time, organic resin fine particles can be arranged on the surface of the toner base particles, and an anionic surfactant containing a carboxyl group can be bound and arranged on the surface of the toner base particles.

[0250] Furthermore, when the toner materials are emulsified or dispersed, an extension reaction and / or crosslinking reaction occurs between the curing agent and the prepolymer, thereby producing an amorphous polyester resin.

[0251] The reaction conditions (reaction time, reaction temperature) for producing the prepolymer are not particularly limited, and can be appropriately selected depending on the combination of the curing agent and the prepolymer.

[0252] The reaction time is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 minutes to 40 hours, more preferably 2 hours to 24 hours.

[0253] The reaction temperature is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0°C to 150°C, more preferably 40°C to 98°C.

[0254] The method for stably forming a dispersion liquid containing a prepolymer in an aqueous medium is not particularly limited and may be appropriately selected depending on the purpose. For example, there is a method in which an oil phase prepared by dissolving or dispersing a toner material in a solvent is added to an aqueous medium phase, and the oil phase is dispersed by shear force.

[0255] The dispersing machine for dispersion is not particularly limited and can be appropriately selected depending on the purpose. Examples of the dispersing machine include a low-speed shear type dispersing machine, a high-speed shear type dispersing machine, a friction type dispersing machine, a high-pressure jet type dispersing machine, and an ultrasonic dispersing machine.

[0256] Among these, a high-speed shear type disperser is preferred because it is possible to control the particle size of the dispersion (oil droplets) to 2 μm to 20 μm.

[0257] When a high-speed shear type dispersing machine is used, the conditions such as the rotation speed, dispersing time, and dispersing temperature can be appropriately selected depending on the purpose.

[0258] The rotation speed is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1,000 rpm to 30,000 rpm, and more preferably 5,000 rpm to 20,000 rpm.

[0259] The dispersion time is not particularly limited and can be appropriately selected depending on the purpose, but in the case of a batch method, it is preferably 0.1 to 5 minutes.

[0260] The dispersion temperature is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0° C. to 150° C. under pressure, and more preferably 40° C. to 98° C. In general, the higher the dispersion temperature, the easier the dispersion.

[0261] The amount of the aqueous medium used when emulsifying or dispersing the toner material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50 parts by mass to 2,000 parts by mass, more preferably 100 parts by mass to 1,000 parts by mass, relative to 100 parts by mass of the toner material. If the amount of the aqueous medium used is less than 50 parts by mass, the dispersion state of the toner material may become poor, and toner base particles of a predetermined particle size may not be obtained. If the amount of the aqueous medium used is more than 2,000 parts by mass, the production cost may increase.

[0262] When emulsifying or dispersing the oil phase containing the toner materials, it is preferable to use a dispersant from the viewpoints of stabilizing the dispersion such as oil droplets, forming a desired shape, and sharpening the particle size distribution.

[0263] The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.

[0264] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. For example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used.

[0265] The anionic surfactant is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include alkylbenzene sulfonate, α-olefin sulfonate, phosphate, etc. Among these, those having a fluoroalkyl group are preferred.

[0266] (Organic solvent removal process) Toner base particles are obtained by removing the organic solvent from the dispersion liquid such as the emulsified slurry. The method for removing the organic solvent from the dispersion liquid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a method of gradually increasing the temperature of the entire reaction system to evaporate the organic solvent in the oil droplets, and a method of spraying the dispersion liquid in a dry atmosphere to remove the organic solvent in the oil droplets.

[0267] When the organic solvent is removed, toner base particles are formed. The toner base particles can be washed, dried, etc., and can further be classified, etc. The classification can be performed by removing fine particles in a liquid using a cyclone, decanter, centrifugal separation, etc., or the classification operation can be performed after drying.

[0268] (External addition process) The obtained toner base particles may be mixed with an external additive, a charge control agent, etc. In this case, by applying a mechanical impact force, it is possible to suppress the particles of the external additive, etc. from being detached from the surface of the toner base particles.

[0269] The method of applying the mechanical impact force can be appropriately selected depending on the purpose, and examples thereof include a method of applying an impact force to the mixture using a blade rotating at high speed, a method of introducing the mixture into a high-speed air current to accelerate it, and causing particles to collide with each other or against an appropriate collision plate, etc.

[0270] The device used in the method of applying a mechanical impact force can be appropriately selected depending on the purpose, and examples include an Angmill (manufactured by Hosokawa Micron Corporation), a device obtained by modifying an I-type mill (manufactured by Japan Pneumatic Mfg. Co., Ltd.) to reduce the grinding air pressure, a Hybridization System (manufactured by Nara Machinery Works, Ltd.), a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), an automatic mortar, and the like.

[0271] Next, the mixture is passed through a sieve of 250 mesh or more to remove coarse particles and aggregated particles, thereby obtaining the toner according to one embodiment.

[0272] <Developer> The developer according to an embodiment includes the toner according to an embodiment, and may include other components, such as a carrier, which are appropriately selected as necessary. This allows the developer to have excellent transferability, chargeability, and the like, and to stably form high-quality images.

[0273] The developer may be a one-component developer or a two-component developer. However, when used in high-speed printers that correspond to the recent improvements in information processing speed, a two-component developer is preferable from the viewpoint of improving the developer life.

[0274] When the toner according to one embodiment is used as a single-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, there is little filming of the toner on the developing roller, and there is little melting of the toner to components such as blades that thin the toner layer, and good and stable developability and images can be obtained even with long-term stirring in the developing device.

[0275] When the developer according to the embodiment is used as a two-component developer, it can be mixed with a carrier and used as a developer. When the toner according to the embodiment is used as a two-component developer, the particle size of the toner is small even if the toner is balanced over a long period of time, and good and stable developability and images can be obtained even when the toner is stirred for a long period of time in a developing device.

[0276] The content of the carrier in the two-component developer can be appropriately selected depending on the purpose, but is preferably 90 parts by mass to 98 parts by mass, and more preferably 93 parts by mass to 97 parts by mass, relative to 100 parts by mass of the two-component developer.

[0277] The developer according to an embodiment can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.

[0278] [Career] The carrier is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the carrier has a core material and a resin layer (coating layer) that coats the core material.

[0279] (Core material) The material of the core material is not particularly limited and can be appropriately selected according to the purpose. For example, manganese-strontium-based material of 50 emu / g to 90 emu / g, manganese-magnesium-based material of 50 emu / g to 90 emu / g, etc. can be mentioned. In order to ensure image density, it is preferable to use high magnetization materials such as iron powder of 100 emu / g or more, magnetite of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetization materials such as copper-zinc-based materials of 30 emu / g to 80 emu / g, because it can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for high image quality. These materials may be used alone or in combination of two or more.

[0280] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 μm to 150 μm, more preferably 40 μm to 100 μm. If the volume average particle diameter is 10 μm or more, the amount of fine powder in the carrier increases, and the magnetization per particle decreases, which can effectively prevent the problem of carrier scattering. On the other hand, if it is 150 μm or less, the specific surface area decreases, which can cause toner scattering, and in full color with many solid parts, the problem of poor reproduction of the solid parts can be effectively prevented.

[0281] (Resin layer) The resin layer can contain a resin and other components as necessary. The resin used in the resin layer can be a known material that can impart the necessary electrostatic property. Specifically, it is preferable to use a silicone resin, an acrylic resin, or a combination of these. In addition, the composition for forming the resin layer preferably contains a silane coupling agent.

[0282] The average thickness of the resin layer is preferably 0.05 to 0.50 μm.

[0283] <Developer container> The developer storage container according to the embodiment stores the developer according to the embodiment. The developer storage container is not particularly limited and can be appropriately selected from known containers, and examples of the developer storage container include a container body and a cap.

[0284] The size, shape, structure, material, etc. of the container body are not particularly limited, but the shape is preferably cylindrical, etc., and the inner surface is formed with spiral irregularities so that the developer content can be transferred to the outlet side by rotating, and it is particularly preferred that a part or all of the spiral irregularities have a bellows function. Furthermore, the material is not particularly limited, but it is preferred that the material has good dimensional accuracy, and examples of such materials include resin materials such as polyester resin, polyethylene resin, polypropylene resin, polystyrene resin, polyvinyl chloride resin, polyacrylic acid, polycarbonate resin, ABS resin, and polyacetal resin.

[0285] The developer storage container is easy to store, transport, and the like, and has excellent handleability, and therefore can be detachably attached to an image forming apparatus, a process cartridge, and the like, which will be described later, and used for replenishing the developer.

[0286] <Toner storage unit> The toner storage unit according to the embodiment can store the toner according to the embodiment. The toner storage unit according to the embodiment refers to a unit having a function of storing toner and storing the toner. Here, examples of the toner storage unit include a toner storage container, a developing unit, and a process cartridge.

[0287] The toner storage container refers to a container that stores toner.

[0288] The developing device has a means for containing toner and developing the toner.

[0289] The process cartridge is a cartridge that integrates at least an electrostatic latent image carrier (also called an image carrier) and a developing means, contains toner, and is detachable from an image forming apparatus. The process cartridge may further include at least one selected from a charging means, an exposure means, a cleaning means, etc.

[0290] The toner storage unit according to the embodiment stores the toner according to the embodiment. By mounting the toner storage unit according to the embodiment on an image forming apparatus and forming an image, the toner according to the embodiment is used to form an image, so that a toner having excellent low-temperature fixing properties, high-temperature offset resistance, heat-resistant storage stability, and chargeability can be obtained.

[0291] <Image forming device> An image forming apparatus according to one embodiment has an electrostatic latent image carrier, an electrostatic latent image forming unit that forms an electrostatic latent image on the electrostatic latent image carrier, and a developing unit that develops the electrostatic latent image formed on the electrostatic latent image carrier with toner to form a toner image, and may further have other components as necessary.

[0292] More preferably, the image forming apparatus according to one embodiment includes, in addition to the electrostatic latent image carrier, electrostatic latent image forming unit, and developing unit described above, a transfer unit that transfers the toner image onto a recording medium, and a fixing unit that fixes the transferred image onto the surface of the recording medium.

[0293] In the developing section, a toner according to an embodiment is used. Preferably, a developer containing the toner according to an embodiment and, if necessary, other components such as a carrier may be used to form a toner image.

[0294] (Electrostatic latent image carrier) The material, shape, structure, size, etc. of the electrostatic latent image carrier (sometimes called "electrophotographic photoreceptor" or "photoreceptor") are not particularly limited and can be appropriately selected from known materials. Examples of materials for the electrostatic latent image carrier include inorganic photoreceptors such as amorphous silicon and selenium, and organic photoreceptors (OPC) such as polysilane and phthalopolymethine. Among these, amorphous silicon is preferred in terms of long life.

[0295] As the amorphous silicon photoreceptor, for example, a photoreceptor having a photoconductive layer made of a-Si formed on the support by heating the support to 50° C. to 400° C. and forming a film on the support by a vacuum deposition method, a sputtering method, an ion plating method, a thermal CVD (chemical vapor deposition) method, a photo CVD method, a plasma CVD method, etc. Among these, the plasma CVD method, that is, a method in which a raw material gas is decomposed by a direct current, a high frequency wave, or a microwave glow discharge to form an a-Si deposition film on the support, is preferable.

[0296] The shape of the electrostatic latent image carrier is not particularly limited and can be appropriately selected depending on the purpose, but is preferably cylindrical. The outer diameter of the cylindrical electrostatic latent image carrier is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 3 mm to 100 mm, more preferably 5 mm to 50 mm, and particularly preferably 10 mm to 30 mm.

[0297] (Electrostatic latent image forming section) The electrostatic latent image forming unit is not particularly limited as long as it is a means for forming an electrostatic latent image on an electrostatic latent image carrier, and can be appropriately selected according to the purpose. The electrostatic latent image forming unit includes, for example, a charging member (charger) for uniformly charging the surface of the electrostatic latent image carrier, and an exposure member (exposure device) for imagewise exposing the surface of the electrostatic latent image carrier.

[0298] The charger is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charger include a contact charger equipped with a conductive or semiconductive roll, brush, film, rubber blade, etc., and a non-contact charger that utilizes corona discharge such as a corotron or scorotron.

[0299] The shape of the charger may be any shape, such as a roller, a magnetic brush, a fur brush, etc., and can be selected according to the specifications and shape of the image forming apparatus.

[0300] The charger is preferably one that is arranged in contact or non-contact with the electrostatic latent image carrier and charges the surface of the electrostatic latent image carrier by applying superimposed DC and AC voltages to the electrostatic latent image carrier. Also, the charger is preferably a charging roller that is arranged in close proximity to the electrostatic latent image carrier in a non-contact manner via a gap tape and charges the surface of the electrostatic latent image carrier by applying superimposed DC and AC voltages to the charging roller.

[0301] The charger is not limited to a contact type charger, but it is preferable to use a contact type charging member since it provides an image forming apparatus in which the amount of ozone generated from the charger is reduced.

[0302] The exposure device is not particularly limited as long as it can expose the surface of the electrostatic latent image carrier charged by the charger in the shape of an image to be formed, and can be appropriately selected depending on the purpose. Examples of the exposure device include various exposure devices such as a copying optical system, a rod lens array system, a laser optical system, and a liquid crystal shutter optical system.

[0303] The light source used in the exposure device is not particularly limited and can be appropriately selected depending on the purpose. Examples of the light source include fluorescent lamps, tungsten lamps, halogen lamps, mercury lamps, sodium lamps, light-emitting diodes (LEDs), semiconductor lasers (LDs), electroluminescence (EL), and other light-emitting materials in general.

[0304] In order to irradiate only light in a desired wavelength range, various filters such as a sharp cut filter, a band pass filter, a near infrared cut filter, a dichroic filter, an interference filter, and a color temperature conversion filter can be used.

[0305] It is also possible to employ a backlight system in which exposure is performed imagewise from the back side of the electrostatic latent image bearing member.

[0306] (Developing section) The developing unit is not particularly limited as long as it can develop the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, and can be appropriately selected according to the purpose. For example, the developing unit can be suitably used one that contains toner and has a developing device that can apply the toner to the electrostatic latent image in a contact or non-contact manner, and a developing device equipped with a toner container is preferable.

[0307] The developing device may be a single-color developing device or a multi-color developing device. As the developing device, for example, a developing device having an agitator that frictionally agitates the toner to charge it, a magnetic field generating unit fixed inside, and a rotatable developer carrier that carries a developer containing toner on its surface is preferable.

[0308] (Transfer section) The transfer section preferably has a first transfer section that transfers a visible image onto an intermediate transfer body to form a composite transfer image, and a second transfer section that transfers the composite transfer image onto a recording medium. The intermediate transfer body is not particularly limited and can be appropriately selected from known transfer bodies depending on the purpose, and a transfer belt or the like is preferably used.

[0309] The transfer section (first transfer means and secondary transfer section) preferably has at least a transfer device that peels and charges a visible image formed on an electrostatic latent image carrier (photoconductor) onto a recording medium. The number of transfer sections may be one or more.

[0310] Examples of the transfer device include a corona transfer device using corona discharge, a transfer belt, a transfer roller, a pressure transfer roller, and an adhesive transfer device.

[0311] The recording medium is typically plain paper, but there are no particular limitations as long as it is capable of transferring the unfixed image after development, and it can be selected appropriately according to the purpose. A PET base for overhead projectors can also be used.

[0312] (Fixing part) The fixing unit is not particularly limited and can be appropriately selected depending on the purpose, but a known heating and pressing unit is suitable. Examples of the heating and pressing unit include a combination of a heating roller and a pressure roller, and a combination of a heating roller, a pressure roller, and an endless belt.

[0313] The fixing section is preferably a heating and pressurizing section having a heating element having a heat generating element, a film in contact with the heating element, and a pressure member in pressure contact with the heating element via the film, and capable of heat-fixing the recording medium on which an unfixed image has been formed by passing the recording medium between the film and the pressure member.

[0314] The heating temperature in the heating and pressurizing section is usually preferably 80°C to 200°C.

[0315] The surface pressure in the heating and pressing section is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 N / cm 2 ~80N / cm 2 It is preferable that:

[0316] In this embodiment, depending on the purpose, for example, a known optical fixing device may be used together with or instead of the fixing unit.

[0317] (others) The image forming apparatus according to the first embodiment may further include, for example, a static eliminator, a recycle unit, a controller, and the like.

[0318] ((Static charge removal section)) The charge removing section is not particularly limited as long as it can apply a charge removing bias to the electrostatic latent image bearing member, and can be appropriately selected from among known charge removers. For example, a charge removing lamp or the like is preferably used.

[0319] (Cleaning Department) The cleaning unit may be any type capable of removing the toner remaining on the electrostatic latent image carrier, and may be appropriately selected from among known cleaners. Examples of the cleaning unit include a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, a blade cleaner, a brush cleaner, and a web cleaner.

[0320] The image forming apparatus according to the first embodiment has a cleaning section, which improves the cleaning performance. That is, by controlling the adhesion between toner particles, the fluidity of the toner is controlled, and the cleaning performance can be improved. In addition, by controlling the characteristics of the toner after deterioration, it is possible to maintain excellent cleaning quality even under severe conditions such as a long life or high temperature and humidity. Furthermore, since the external additive can be sufficiently liberated from the toner on the photoreceptor, a deposition layer (dam layer) of the external additive in the cleaning blade nip can be formed, thereby achieving high cleaning performance.

[0321] (Recycling Department) The recycling section is not particularly limited, and examples thereof include known conveying means.

[0322] ((Control Unit)) The control unit can control the movement of each of the above-mentioned parts. The control unit is not particularly limited as long as it can control the movement of each of the above-mentioned parts, and can be appropriately selected depending on the purpose. For example, the control unit can be a control device such as a sequencer or a computer.

[0323] The image forming apparatus according to an embodiment can form images using the toner according to an embodiment, and therefore can reduce power consumption and stably provide high-quality images.

[0324] <Image forming method> An image forming method according to an embodiment includes an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier, and a developing step of developing the electrostatic latent image with toner to form a toner image, and may further include other steps as necessary. The image forming method can be suitably performed by the image forming apparatus, the electrostatic latent image forming step can be suitably performed by the electrostatic latent image forming unit, the developing step can be suitably performed by the developing unit, and the other steps can be suitably performed by the other units.

[0325] Furthermore, the image forming method according to one embodiment more preferably includes, in addition to the electrostatic latent image forming process and the developing process described above, a transfer process of transferring the toner image onto a recording medium, and a fixing process of fixing the transferred image onto the surface of the recording medium.

[0326] In the developing step, the toner according to an embodiment is used. Preferably, a developer containing the toner according to an embodiment and, if necessary, other components such as a carrier may be used to form a toner image.

[0327] The electrostatic latent image forming process is a process of forming an electrostatic latent image on an electrostatic latent image carrier, and includes a charging process of charging the surface of the electrostatic latent image carrier and an exposure process of exposing the charged surface of the electrostatic latent image carrier to light to form an electrostatic latent image. Charging can be performed, for example, by applying a voltage to the surface of the electrostatic latent image carrier using a charger. Exposure can be performed, for example, by exposing the surface of the electrostatic latent image carrier to light in an imagewise manner using the exposure device. The electrostatic latent image can be formed, for example, by uniformly charging the surface of the electrostatic latent image carrier and then exposing it to light in an imagewise manner, and can be performed by an electrostatic latent image forming unit.

[0328] The developing step is a step of sequentially developing the electrostatic latent image with toners of multiple colors to form a visible image. The visible image can be formed, for example, by developing the electrostatic latent image with the toners, using a developing device.

[0329] In the developing device, for example, toner and carrier are mixed and stirred, and the toner becomes charged by friction during this process and is held in a standing state on the surface of the rotating magnet roller, forming a magnetic brush. Since the magnet roller is disposed near an electrostatic latent image carrier (photoconductor), a part of the toner constituting the magnetic brush formed on the surface of the magnet roller moves to the surface of the electrostatic latent image carrier (photoconductor) by electrical attraction. As a result, the electrostatic latent image is developed by the toner, and a visible image made of the toner is formed on the surface of the electrostatic latent image carrier (photoconductor).

[0330] The transfer step is a step of transferring a visible image to a recording medium. The transfer step is preferably performed using an intermediate transfer body, and after the visible image is primarily transferred onto the intermediate transfer body, the visible image is secondarily transferred onto the recording medium. The transfer step is more preferably performed using toner of two or more colors, preferably full-color toner, and includes a primary transfer step of transferring the visible image onto the intermediate transfer body to form a composite transfer image, and a secondary transfer step of transferring the composite transfer image onto the recording medium. The transfer can be performed, for example, by charging an electrostatic latent image carrier (photoconductor) with a transfer charger, and can be performed by a transfer section.

[0331] The fixing process is a process in which the visible image transferred to the recording medium is fixed using a fixing device, and may be performed for each color developer each time it is transferred to the recording medium, or may be performed simultaneously for each color developer in a stacked state.

[0332] The image forming method according to the first embodiment may further include other steps appropriately selected as necessary, such as a static elimination step, a cleaning step, a recycling step, and the like.

[0333] The charge removing step is a step of removing electricity by applying a charge removing bias to the electrostatic latent image bearing member, and can be suitably performed by the charge removing unit.

[0334] The cleaning step is a step of removing the toner remaining on the electrostatic latent image bearing member, and can be suitably performed by a cleaning unit.

[0335] The recycling step is a step in which the toner removed in the cleaning step is recycled to the developing unit, and can be suitably carried out by the recycling unit.

[0336] The image forming method according to an embodiment can form an image using the toner according to an embodiment, and therefore can reduce power consumption and stably provide high-quality images.

[0337] [One embodiment of the image forming apparatus] Next, one aspect of an image forming apparatus according to an embodiment will be described with reference to Fig. 1. Fig. 1 is a schematic diagram showing an example of an image forming apparatus according to an embodiment. As shown in Fig. 1, the image forming apparatus 1A includes a photoconductor drum 10 which is an electrostatic latent image carrier, a charging roller 20 which is a charging section, an exposure device 30 which is an exposure section, a developing device 40 which is a developing section, an intermediate transfer body (intermediate transfer belt) 50, a cleaning device 60 which is a cleaning section, a transfer roller 70 which is a transfer section, a static elimination lamp 80 which is a static elimination section, and an intermediate transfer body cleaning device 90.

[0338] The intermediate transfer body 50 is an endless belt stretched by three rollers 51 arranged inside, and is designed to be movable in the direction of the arrow by the three rollers 51. Some of the three rollers 51 also function as transfer bias rollers that can apply a predetermined transfer bias (primary transfer bias) to the intermediate transfer body 50. An intermediate transfer body cleaning device 90 is arranged near the intermediate transfer body 50. Furthermore, a transfer roller 70 is arranged facing the intermediate transfer body 50 near the intermediate transfer body 50, and can apply a transfer bias (secondary transfer bias) for transferring (secondary transfer) a developed image (toner image) to a transfer paper P as a recording medium. Around the intermediate transfer body 50, a corona charger 52 for applying a charge to the toner image on the intermediate transfer body 50 is arranged between the contact portion between the photosensitive drum 10 and the intermediate transfer body 50 and the contact portion between the intermediate transfer body 50 and the transfer paper P with respect to the rotation direction of the intermediate transfer body 50.

[0339] The developing device 40 is composed of a developing belt 41 which is a developer carrier, and a black (Bk) developing unit 42K, a yellow (Y) developing unit 42Y, a magenta (M) developing unit 42M, and a cyan (C) developing unit 42C which are arranged around the developing belt 41.

[0340] The developing belt 41 is an endless belt that is stretched around a plurality of belt rollers and can move in the direction of the arrow in the figure. Furthermore, a part of the developing belt 41 is in contact with the photoconductor drum 10.

[0341] The black developing unit 42K includes a developer container 421K, a developer supply roller 422K, and a developing roller (developer carrier) 423K. The yellow developing unit 42Y includes a developer container 421Y, a developer supply roller 422Y, and a developing roller 423Y. The magenta developing unit 42M includes a developer container 421M, a developer supply roller 422M, and a developing roller 423M. The cyan developing unit 42C includes a developer container 421C, a developer supply roller 422C, and a developing roller 423C.

[0342] Next, a method of forming an image using the image forming apparatus 1 will be described. First, the surface of the photosensitive drum 10 is uniformly charged using the charging roller 20, and then the photosensitive drum 10 is exposed to exposure light L using the exposure device 30 to form an electrostatic latent image. Next, the electrostatic latent image formed on the photosensitive drum 10 is developed with toner supplied from the developing device 40 to form a toner image. Furthermore, the toner image formed on the photosensitive drum 10 is transferred (primary transfer) onto the intermediate transfer body 50 by the transfer bias applied from the roller 51, and then transferred (secondary transfer) onto the transfer paper P fed by a paper feed unit (not shown) by the transfer bias applied from the transfer roller 70. Meanwhile, the photosensitive drum 10 on which the toner image has been transferred to the intermediate transfer body 50 has the toner remaining on its surface removed by the cleaning device 60, and is then discharged by the discharge lamp 80. The residual toner on the intermediate transfer body 50 after the image transfer is removed by the intermediate transfer body cleaning device 90.

[0343] After the transfer process is completed, the transfer paper P is transported to a fixing unit, where the transferred toner image is fixed onto the transfer paper P.

[0344] Fig. 2 is a schematic diagram showing another example of an image forming apparatus according to an embodiment. As shown in Fig. 2, the image forming apparatus 1B has the same configuration as the image forming apparatus 1A shown in Fig. 1, except that the developing belt 41 is not provided, and a black developing unit 42K, a yellow developing unit 42Y, a magenta developing unit 42M, and a cyan developing unit 42C are arranged directly opposite each other around the photoconductor drum 10.

[0345] Fig. 3 is a schematic diagram showing another example of an image forming apparatus according to an embodiment. As shown in Fig. 3, the image forming apparatus 1C is a tandem type color image forming apparatus, and includes a copying machine main body 110, a paper feed table 120, a scanner 130, an automatic document feeder (ADF) 140, a secondary transfer device 150, a fixing device 160 which is a fixing section, and a sheet reversing device 170.

[0346] An endless belt-like intermediate transfer body 50 is provided in the center of the copying machine main body 110. The intermediate transfer body 50 is an endless belt stretched around three rollers 53A, 53B, and 53C, and can move in the direction of the arrow in FIG. 3. An intermediate transfer body cleaning device 90 is disposed near the roller 53B for removing toner remaining on the intermediate transfer body 50 after the toner image has been transferred to the recording paper. Facing the intermediate transfer body 50 stretched around the rollers 53A and 53B, image forming units (yellow (Y) development unit 42Y, cyan (C) development unit 42C, magenta (M) development unit 42M, and black (Bk) development unit 42K) are disposed along the transport direction.

[0347] Further, an exposure device 30 is disposed near the image forming units. Furthermore, a secondary transfer device 150 is disposed on the side of the intermediate transfer body 50 opposite to the side on which the image forming units are disposed. The secondary transfer device 150 includes a secondary transfer belt 151. The secondary transfer belt 151 is an endless belt stretched over a pair of rollers 152, and the recording paper transported on the secondary transfer belt 151 and the intermediate transfer body 50 can come into contact with each other between roller 53C and roller 152.

[0348] In addition, a fixing device 160 is disposed near the secondary transfer belt 151. The fixing device 160 includes a fixing belt 161, which is an endless belt stretched over a pair of rollers, and a pressure roller 162 disposed so as to be pressed against the fixing belt 161.

[0349] Further, near the secondary transfer belt 151 and the fixing device 160, a sheet reversing device 170 is disposed for reversing the recording paper when images are formed on both sides of the recording paper.

[0350] Next, a method of forming a full-color image using the image forming apparatus 1C will be described. First, a color original is set on the platen 141 of the automatic document feeder (ADF) 140, or the automatic document feeder 140 is opened and a color original is set on the contact glass 131 of the scanner 130, and the automatic document feeder 140 is closed.

[0351] When a start switch (not shown) is pressed and a color original is set on the automatic original feeder 140, the color original is fed and moved onto the contact glass 131, and then the scanner 130 is driven and the first and second traveling bodies 132 and 133 equipped with light sources move. On the other hand, immediately after an original is set on the contact glass 131, the scanner 130 is driven and the first and second traveling bodies 132 and 133 equipped with light sources move. At this time, the light reflected from the original surface of the light irradiated from the first traveling body 132 is reflected by the mirror of the second traveling body 133 and then received by the reading sensor 136 through the imaging lens 135, whereby the color original (color image) is read and image information of black, yellow, magenta, and cyan is obtained.

[0352] The image information of each color is transmitted to the developing units of each color (yellow developing unit 42Y, cyan developing unit 42C, magenta developing unit 42M, and black developing unit 42K), respectively, and a toner image of each color is formed.

[0353] Fig. 4 is a partial enlarged view of the image forming apparatus of Fig. 3. As shown in Fig. 4, each developing unit (yellow developing unit 42Y, cyan developing unit 42C, magenta developing unit 42M, and black developing unit 42K) includes a photoconductor drum 10 (black static photoconductor drum 10K, yellow photoconductor drum 10Y, magenta photoconductor drum 10M, and cyan photoconductor drum 10C), a charging roller 20 as a charging unit that uniformly charges the electrostatic latent image carrier 10, an exposure device 30 that exposes the photoconductor drum 10 to exposure light L based on image information of each color and forms an electrostatic latent image of each color on the photoconductor drum 10, a developing device 40 as a developing unit that develops the electrostatic latent image with a developer of each color to form a toner image of each color, a transfer charger 62 for transferring the toner image onto the intermediate transfer body 50, a cleaning device 60, and a discharge lamp 80.

[0354] The toner images of each color formed by the developing units of each color (yellow developing unit 42Y, cyan developing unit 42C, magenta developing unit 42M, and black developing unit 42K) are sequentially transferred (primary transfer) onto intermediate transfer body 50, which moves while being stretched around rollers 53A, 53B, and 53C. Then, the toner images of each color are superimposed on intermediate transfer body 50 to form a composite toner image.

[0355] Meanwhile, in the paper feed table 120, one of the paper feed rollers 121 is selectively rotated to feed recording paper from one of the paper feed cassettes 123 provided in multiple stages in a paper bank 122. The recording paper is separated one by one by a separation roller 124 and sent to a paper feed path 125, transported by a transport roller 126, guided to a paper feed path 111 in the copying machine main body 110, and stopped by abutting against a registration roller 112. Alternatively, the manual feed roller 113 is rotated to feed recording paper on a manual feed tray 114, which is separated one by one by the manual feed roller 113 and guided to a manual feed path 115, and stopped by abutting against a registration roller 112.

[0356] The registration rollers 112 are generally grounded when in use, but may be used with a bias applied to them in order to remove paper dust from the recording paper.

[0357] Next, the registration roller 112 is rotated in synchronization with the composite toner image formed on the intermediate transfer body 50, and a recording paper is sent between the intermediate transfer body 50 and the secondary transfer belt 151, and the composite toner image is transferred (secondary transfer) onto the recording paper. Note that the toner remaining on the intermediate transfer body 50 after the composite toner image has been transferred is removed by the intermediate transfer body cleaning device 90.

[0358] The recording paper onto which the composite toner image has been transferred is transported by a secondary transfer belt 151, and then the composite toner image is fixed onto the recording paper by a fixing device 160.

[0359] Thereafter, the conveying path of the recording paper is switched by the switching claw 116, and the recording paper is discharged onto the paper discharge tray 118 by the discharge rollers 117. Alternatively, the conveying path of the recording paper is switched by the switching claw 116, the recording paper is inverted by the sheet inverting device 170, and is again guided to the secondary transfer belt 151, and after an image is formed on the back side in the same manner, the recording paper is discharged onto the paper discharge tray 118 by the discharge rollers 117.

[0360] <Process cartridge> The process cartridge according to one embodiment is molded so as to be detachably attached to various image forming devices, and has an electrostatic latent image carrier that carries an electrostatic latent image, and a developing unit that develops the electrostatic latent image carried on the electrostatic latent image carrier with a developer according to the above-mentioned one embodiment to form a toner image, and may have other configurations as necessary.

[0361] The electrostatic latent image carrier is the same as the electrostatic latent image carrier of the image forming apparatus described above, and therefore details thereof will be omitted.

[0362] The developing unit includes a developer container that contains the developer according to an embodiment, and a developer carrier that carries and transports the developer contained in the developer container. The developing unit may further include a regulating member or the like to regulate the thickness of the developer carried by the developer container.

[0363] An example of a process cartridge according to an embodiment is shown in Fig. 5. As shown in Fig. 5, the image forming apparatus process cartridge 200 includes a photosensitive drum 10, a corona charger 22 as a charging unit, a developing device 40, a cleaning device 60, and a transfer roller 70. EXAMPLES

[0364] The embodiments will be described in more detail below with reference to examples and comparative examples, but the embodiments are not limited to these examples and comparative examples.

[0365] <Preparation of surfactant 1> Hydrochloric acid was added to 200 parts by mass of disodium dodecyl sulfosuccinate (Viewlite SSS, manufactured by Sanyo Chemical Industries, Ltd.) until the pH reached 3.0, and the mixture was stirred for 30 minutes. The filtrate was then collected by suction filtration, and the solid content was adjusted to 30% with ion-exchanged water to obtain Surfactant 1.

[0366] The obtained surfactant 1 was analyzed by liquid chromatography (AQUITY-UPLC / SQD system, manufactured by Nihon Waters) to confirm that an anionic surfactant having a carboxyl group was obtained from the peak of the MS detector. The acid value was measured using an automatic potentiometric titrator (DL-53 Titrator, manufactured by Mettler Toledo) and was found to be 140 mgKOH / g.

[0367] <Preparation of Surfactant 2> Hydrochloric acid was added to 200 parts by mass of octyl sulfosuccinate (Pelex OT-P, manufactured by Kao Corporation) until the pH reached 5.0, and the mixture was stirred for 30 minutes. The filtrate was then collected by suction filtration, and the solid content was adjusted to 30% with ion-exchanged water to obtain Surfactant 2.

[0368] The obtained surfactant 2 was analyzed by liquid chromatography (AQUITY-UPLC / SQD system, manufactured by Nihon Waters) and confirmed to be an anionic surfactant having a carboxyl group from the peak of the MS detector. The acid value was measured using an automatic potentiometric titrator (DL-53 Titrator, manufactured by Mettler Toledo) and was found to be 170 mgKOH / g.

[0369] <Preparation of surfactant 3> After maleic acid and pentanol were reacted in equimolar amounts, sodium sulfite was reacted with maleic acid in equimolar amounts. Hydrochloric acid was added until the pH was 5.0, and the mixture was stirred for 30 minutes. The filtrate was then collected by suction filtration, and the solid content was adjusted to 30% with ion-exchanged water to obtain surfactant 3.

[0370] The obtained surfactant 3 was analyzed by liquid chromatography (AQUITY-UPLC / SQD system, manufactured by Nihon Waters) and confirmed to be an anionic surfactant having a carboxyl group from the peak of the MS detector. The acid value was measured using an automatic potentiometric titrator (DL-53 Titrator, manufactured by Mettler Toledo) and was found to be 190 mgKOH / g.

[0371] <Preparation of Surfactant 4> After maleic acid and pentadecanol were reacted in equimolar amounts, sodium sulfite was reacted with maleic acid in equimolar amounts. Hydrochloric acid was added until the pH was 5.0, and the mixture was stirred for 30 minutes. The filtrate was then collected by suction filtration, and the solid content was adjusted to 30% with ion-exchanged water to obtain surfactant 4.

[0372] The obtained surfactant 4 was analyzed by liquid chromatography (AQUITY-UPLC / SQD system, manufactured by Nihon Waters) and confirmed to be an anionic surfactant having a carboxyl group from the peak of the MS detector. The acid value was measured by an automatic potentiometric titrator (DL-53 Titrator, manufactured by Mettler Toledo) and was found to be 110 mgKOH / g.

[0373] The acid values ​​of each of Surfactant 1 to Surfactant 4 are shown in Table 1.

[0374] [Table 1]

[0375] <Organic resin fine particle production example 1> [Production of microparticle dispersion (W-01) containing organic resin microparticles (A-1S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 450 parts by mass of styrene, 250 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was added dropwise over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-01) containing organic resin fine particles (A-1S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-01) was adjusted so that the pure polymer content was 20%.

[0376] The volume average particle diameter of the organic resin fine particles (A-1S) in the fine particle dispersion (W-01) was 15.0 nm. A part of the fine particle dispersion (W-01) was dried to isolate the organic resin fine particles (A-1S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-1S) were 1st The measurement results of the acid value are shown in Table 2.

[0377] <Organic resin fine particle production example 2> [Production of Microparticle Dispersion (W-1) Containing Organic Resin Microparticles (A-1)] Next, 667 parts by mass of the microparticle dispersion (W-01) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H), the mixture was heated to raise the temperature in the system to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-1) containing organic resin microparticles (A-1) containing resin (a) (A-1C) and resin (b) (A-1S), which are polymers obtained by copolymerizing styrene and butyl acrylate, as constituents in the same particle, using the organic resin microparticles (A-1S) in the microparticle dispersion (W-01) as seeds. The fine particle dispersion (W-1) was adjusted so that the pure polymer content was 20%.

[0378] The organic resin fine particles (A-1) had a volume average particle size of 17.3 nm, which was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0379] In addition, the fine particle dispersion (W-1) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-1C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0380] It was confirmed that the microparticle dispersion (W-1) contained organic resin microparticles (A-1) by drying a portion of the microparticle dispersion (W-1) and isolating the organic resin microparticles (A-1), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0381] Volume average particle size of organic resin fine particles (A-1), glass transition temperature Tg at the first heating time of differential scanning calorimetry of resin (a) (A-1C) 1st The measurement results of the acid value are shown in Table 2.

[0382] <Organic resin fine particle production example 3> [Production of microparticle dispersion (W-02) containing resin microparticles (A-2S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3760 parts by mass of water and 150 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 430 parts by mass of styrene, 270 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-02) containing organic resin fine particles (A-2S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-02) was adjusted so that the pure polymer content was 20%.

[0383] The volume average particle diameter of the organic resin fine particles (A-2S) in the fine particle dispersion (W-02) was 30.0 nm. A part of the fine particle dispersion (W-02) was dried to isolate the organic resin fine particles (A-2S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-2S) were 1st The measurement results of the acid value are shown in Table 2.

[0384] <Organic resin fine particle production example 4> [Production of Microparticle Dispersion (W-2) Containing Resin Microparticles (A-2)] Next, 667 parts by mass of the microparticle dispersion (W-02) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.) was added, and the system was heated to raise the temperature to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of 1% by mass aqueous ascorbic acid solution were dropped into the mixed solution over 2 hours. After the dropping, the mixed solution was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-2) containing resin microparticles (A-2) containing resin (a) (A-2C) and resin (b) (A-2S) as constituents in the same particle, which are polymers obtained by copolymerizing styrene, butyl acrylate, and an aqueous ascorbic acid solution, using the organic resin microparticles (A-2S) in the microparticle dispersion (W-02) as seeds. The fine particle dispersion (W-2) was adjusted so that the pure polymer content was 20%.

[0385] The volume average particle diameter of the organic resin fine particles (A-2) was 34.3 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) above.

[0386] In addition, the fine particle dispersion (W-2) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-2C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0387] It was confirmed that the microparticle dispersion (W-2) contained organic resin microparticles (A-2) by drying a portion of the microparticle dispersion (W-2) and isolating the organic resin microparticles (A-2), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0388] Volume average particle size of organic resin particles (A-2), glass transition temperature Tg of resin (a) (A-2C) 1st The measurement results of the acid value are shown in Table 2.

[0389] <Organic resin fine particle production 5> [Production of microparticle dispersion (W-03) containing resin microparticles (A-3S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3810 parts by mass of water and 100 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added, and then a mixture of 400 parts by mass of styrene, 300 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-03) containing organic resin fine particles (A-3S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-03) was adjusted so that the pure polymer content was 20%.

[0390] The volume average particle diameter of the organic resin fine particles (A-3S) in the fine particle dispersion (W-03) was 45.0 nm. A part of the fine particle dispersion (W-03) was dried to isolate the organic resin fine particles (A-3S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-3S) were 53°C and 195mgKOH / g, respectively. 1st The measurement results of the acid value are shown in Table 2.

[0391] <Organic resin fine particle production example 6> [Production of Microparticle Dispersion (W-3) Containing Resin Microparticles (A-3)] Next, 667 parts by mass of the microparticle dispersion (W-03) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H) was added, and the system was heated to raise the temperature to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-3) containing resin microparticles (A-3) containing resin (a) (A-3C) and resin (b) (A-3S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-3S) in the microparticle dispersion (W-03) as seeds. The fine particle dispersion (W-3) was adjusted so that the pure polymer content was 20%.

[0392] The volume average particle diameter of the organic resin fine particles (A-3) was 51.5 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) above.

[0393] In addition, the fine particle dispersion (W-3) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-3C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0394] It was confirmed that the microparticle dispersion (W-3) contained organic resin microparticles (A-3) by drying a portion of the microparticle dispersion (W-3) and isolating the organic resin microparticles (A-3), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0395] Volume average particle size of organic resin particles (A-3), glass transition temperature Tg of resin (a) (A-3C) 1st The measurement results of the acid value are shown in Table 2.

[0396] <Organic resin fine particle production example 7> [Production of aqueous dispersion (W-04) containing organic resin fine particles (A-4S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 300 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. The mixture was heated to raise the temperature inside the system to 75°C, and then 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added, followed by dropping a mixture of 450 parts by mass of styrene, 250 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid over a period of 4 hours. After dropping, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-04) containing organic resin fine particles (A-4S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-04) was adjusted so that the pure polymer content was 20%.

[0397] The volume average particle diameter of the organic resin fine particles (A-4S) in the fine particle dispersion (W-04) was 8.0 nm. A part of the fine particle dispersion (W-04) was dried to isolate the organic resin fine particles (A-4S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-4S) were 1st The measurement results of the acid value are shown in Table 2.

[0398] <Organic resin fine particle production example 8> [Production of Microparticle Dispersion (W-4) Containing Organic Resin Microparticles (A-4)] A reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer was charged with 667 parts by mass of the microparticle dispersion (W-04) and 248 parts by mass of water, and 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H) was added, followed by heating to raise the temperature in the system to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-4) containing resin microparticles (A-4) containing resin (a) (A-4C) and resin (b) (A-4S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the microparticles in (W-01) as seeds. The microparticle dispersion (W-4) was adjusted so that the polymer pure content was 20%.

[0399] The volume average particle diameter of the resin fine particles (A-4) was 10.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) described above.

[0400] In addition, the fine particle dispersion (W-4) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-4C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0401] It was confirmed that the microparticle dispersion (W-4) contained organic resin microparticles (A-4) by drying a portion of the microparticle dispersion (W-4) and isolating the organic resin microparticles (A-4), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0402] Volume average particle size of organic resin particles (A-4), glass transition temperature Tg of resin (a) (A-4C) 1st The measurement results of the acid value are shown in Table 2.

[0403] <Organic resin fine particle production example 9> [Production of microparticle dispersion (W-05) containing organic resin microparticles (A-5S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 50 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 450 parts by mass of styrene, 250 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was added dropwise over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-05) containing organic resin fine particles (A-5S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-05) was adjusted so that the pure polymer content was 20%.

[0404] The volume average particle diameter of the organic resin fine particles (A-5S) in the fine particle dispersion (W-05) was 88.0 nm. A part of the fine particle dispersion (W-05) was dried to isolate the organic resin fine particles (A-5S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-5S) were 1st The measurement results of the acid value are shown in Table 2.

[0405] <Organic resin fine particle production example 10> [Production of Microparticle Dispersion (W-5) Containing Organic Resin Microparticles (A-5)] 667 parts by mass of the microparticle dispersion (W-05) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.) was added, and the system was heated to raise the temperature to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous solution of ascorbic acid were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-5) containing resin microparticles (A-5) containing resin (a) (A-5C) and resin (b) (A-4S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the microparticles in the microparticle dispersion (W-01) as seeds. The microparticle dispersion (W-5) was adjusted so that the polymer pure content was 20%.

[0406] The volume average particle diameter of the resin fine particles (A-5) was 100.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) described above.

[0407] In addition, the fine particle dispersion (W-5) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-5C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0408] It was confirmed that the microparticle dispersion (W-5) contained organic resin microparticles (A-5) by drying a portion of the microparticle dispersion (W-5) and isolating the organic resin microparticles (A-5), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0409] Volume average particle size of organic resin particles (A-5), glass transition temperature Tg of resin (a) (A-5C) 1st The measurement results of the acid value are shown in Table 2.

[0410] <Organic resin fine particle production example 11> [Production of Microparticle Dispersion (W-6) Containing Organic Resin Microparticles (A-6)] A reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer was charged with 667 parts by mass of the microparticle dispersion (W-01) and 248 parts by mass of water, and 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H) was added, followed by heating to raise the temperature in the system to 70°C. Then, 23.3 parts by mass of styrene, 43.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-6) containing resin microparticles (A-6) containing resin (a) (A-6C) and resin (b) (A-1S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the microparticles in the microparticle dispersion (W-01) as seeds. The microparticle dispersion (W-6) was adjusted so that the polymer pure content was 20%.

[0411] The volume average particle diameter of the resin fine particles (A-6) was 17.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) described above.

[0412] In addition, the fine particle dispersion (W-6) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-6C). 1st The temperature was 30°C and the acid value was 0 mgKOH / g.

[0413] It was confirmed that the microparticle dispersion (W-6) contained resin microparticles (A-6) by drying a portion of the microparticle dispersion (W-6) and isolating the organic resin microparticles (A-6), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0414] Volume average particle size of organic resin particles (A-6), glass transition temperature Tg of resin (a) (A-6C) 1st The measurement results of the acid value are shown in Table 2.

[0415] <Organic resin fine particle production example 12> [Production of Microparticle Dispersion (W-7) Containing Organic Resin Microparticles (A-7)] A reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer was charged with 667 parts by mass of the microparticle dispersion (W-01) and 248 parts by mass of water, and 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.) was added, followed by heating to raise the temperature in the system to 70°C. Then, 53.3 parts by mass of styrene, 13.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous solution of ascorbic acid were dropped over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-7) containing organic resin microparticles (A-7) containing resin (a) (A-7C) and resin (b) (A-1S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the microparticles in the microparticle dispersion (W-01) as seeds. The microparticle dispersion (W-7) was adjusted so that the polymer pure content was 20%.

[0416] The volume average particle diameter of the resin fine particles (A-7) was 17.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) described above.

[0417] In addition, the fine particle dispersion (W-7) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-7C). 1st The temperature was 70°C and the acid value was 0 mgKOH / g.

[0418] It was confirmed that the microparticle dispersion (W-7) contained organic resin microparticles (A-7) by drying a portion of the microparticle dispersion (W-7) and isolating the organic resin microparticles (A-5), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0419] Volume average particle size of organic resin particles (A-7), glass transition temperature Tg of resin (a) (A-7C) 1st The measurement results of the acid value are shown in Table 2.

[0420] <Organic resin fine particle production example 13> [Production of Microparticle Dispersion (W-8) Containing Organic Resin Microparticles (A-8)] 667 parts by mass of the microparticle dispersion (W-01) and 57 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and 0.06 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.) was added, and the system was heated to raise the temperature to 70°C. Then, 9.6 parts by mass of styrene, 5.2 parts by mass of butyl acrylate, and 4 parts by mass of a 1% by mass aqueous solution of ascorbic acid were dropped into the mixed liquid over 2 hours. After the dropping, the mixed liquid was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-8) containing organic resin microparticles (A-8) containing resin (a) (A-8C) and resin (b) (A-1S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the microparticles in the microparticle dispersion (W-01) as seeds. The microparticle dispersion (W-8) was adjusted so that the polymer pure content was 20%.

[0421] The volume average particle diameter of the resin fine particles (A-8) was 15.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1) described above.

[0422] In addition, the fine particle dispersion (W-8) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-8C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0423] It was confirmed that the microparticle dispersion (W-8) contained organic resin microparticles (A-8) by drying a portion of the microparticle dispersion (W-8) and isolating the organic resin microparticles (A-8), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0424] Volume average particle size of organic resin particles (A-8), glass transition temperature Tg of resin (a) (A-8C) 1stThe measurement results of the acid value are shown in Table 2.

[0425] <Organic resin fine particle production example 14> [Production of Microparticle Dispersion (W-9) Containing Organic Resin Microparticles (A-9)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. The mixture was heated to raise the temperature inside the system to 75°C, and then 90 parts by mass of a 10% by mass ammonium persulfate aqueous solution was added to the mixture, and then a mixture consisting of 640 parts by mass of styrene and 360 parts by mass of butyl acrylate was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-9) containing organic resin fine particles (A-9) containing resin (a) (A-9C) and resin (b) (A-1S) as constituents in the same particle, which are polymers obtained by copolymerizing a mixture consisting of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-9) was adjusted so that the pure polymer content was 20%.

[0426] The volume average particle diameter of the fine particles in the fine particle dispersion (W-9) was 15.0 nm. The volume average particle diameter was measured in the same manner as for the organic resin fine particles (A-1).

[0427] A part of the fine particle dispersion (W-9) was dried to isolate resin (a) (A-9C). The glass transition temperature Tg of resin (a) (A-9C) at the first heating run in differential scanning calorimetry was 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0428] <Organic resin fine particle production example 15> [Production of microparticle dispersion (W-010) containing organic resin microparticles (A-10S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 122 parts by mass of styrene, 578 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-010) containing organic resin fine particles (A-10S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-010) was adjusted so that the pure polymer content was 20%.

[0429] The volume average particle diameter of the organic resin fine particles (A-10S) in the fine particle dispersion (W-010) was 15.0 nm. A part of the fine particle dispersion (W-010) was dried to isolate the organic resin fine particles (A-10S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-11S) were 1st The measurement results of the acid value are shown in Table 3.

[0430] <Organic resin fine particle production example 16> [Production of Microparticle Dispersion (W-10) Containing Organic Resin Microparticles (A-10)] Next, 667 parts by mass of the microparticle dispersion (W-010) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.), the mixture was heated to raise the temperature in the system to 70°C. Then, 13.4 parts by mass of styrene, 53.2 parts by mass of butyl acrylate, and 18.0 parts by mass of 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-10) containing organic resin microparticles (A-10) containing resin (a) (A-10C) and resin (b) (A-10S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-10S) in the microparticle dispersion (W-010) as seeds. The fine particle dispersion (W-10) was adjusted so that the pure polymer content was 20%.

[0431] The organic resin fine particles (A-10) had a volume average particle diameter of 17.3 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0432] In addition, the fine particle dispersion (W-10) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (a) (A-10C). 1st The temperature was 21°C and the acid value was 0 mgKOH / g.

[0433] It was confirmed that the microparticle dispersion (W-10) contained organic resin microparticles (A-10) by drying a portion of the microparticle dispersion (W-10) and isolating the organic resin microparticles (A-10), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0434] Volume average particle size of organic resin fine particles (A-10), glass transition temperature Tg of resin (b) (A-10C) at the first heating time in differential scanning calorimetry 1st The measurement results of the acid value are shown in Table 3.

[0435] <Organic resin fine particle production example 17> [Production of microparticle dispersion (W-011) containing organic resin microparticles (A-11S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 235 parts by mass of styrene, 465 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-011) containing organic resin fine particles (A-11S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-011) was adjusted so that the pure polymer content was 20%.

[0436] The volume average particle diameter of the organic resin fine particles (A-11S) in the fine particle dispersion (W-011) was 15.0 nm. A part of the fine particle dispersion (W-011) was dried to isolate the organic resin fine particles (A-11S). The glass transition temperature Tg 1st The temperature was 30°C and the acid value was 195 mgKOH / g. The volume average particle size and glass transition temperature Tg of the organic resin fine particles (A-11S) were 1st The measurement results of the acid value are shown in Table 3.

[0437] <Organic resin fine particle production example 18> [Production of Microparticle Dispersion (W-11) Containing Organic Resin Microparticles (A-11)] Next, 667 parts by mass of the microparticle dispersion (W-011) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.), the mixture was heated to raise the temperature in the system to 70°C. Then, 23.3 parts by mass of styrene, 43.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-11) containing organic resin microparticles (A-11) containing resin (a) (A-11C) and resin (b) (A-11S), which are polymers obtained by copolymerizing styrene and butyl acrylate, as constituents in the same particle, using the organic resin microparticles (A-11S) in the microparticle dispersion (W-011) as seeds. The fine particle dispersion (W-11) was adjusted so that the pure polymer content was 20%.

[0438] The organic resin fine particles (A-11) had a volume average particle diameter of 17.3 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0439] In addition, the fine particle dispersion (W-11) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (b) (A-11C). 1st The temperature was 31°C and the acid value was 0 mgKOH / g.

[0440] It was confirmed that the microparticle dispersion (W-11) contained organic resin microparticles (A-11) by drying a portion of the microparticle dispersion (W-11) and isolating the organic resin microparticles (A-11), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0441] Volume average particle size of organic resin particles (A-11), glass transition temperature Tg at the first heating time of differential scanning calorimetry of resin (a) (A-11C) 1st The measurement results of the acid value are shown in Table 3.

[0442] <Organic resin fine particle production example 19> [Production of microparticle dispersion (W-012) containing organic resin microparticles (A-12S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 506 parts by mass of styrene, 194 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-012) containing organic resin fine particles (A-12S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-012) was adjusted so that the pure polymer content was 20%.

[0443] The volume average particle diameter of the organic resin fine particles (A-12S) in the fine particle dispersion (W-012) was 15.0 nm. A part of the fine particle dispersion (W-012) was dried to isolate the organic resin fine particles (A-12S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-12S) were 1st The measurement results of the acid value are shown in Table 3.

[0444] <Organic resin fine particle production example 20> [Production of Microparticle Dispersion (W-12) Containing Organic Resin Microparticles (A-12)] Next, 667 parts by mass of the microparticle dispersion (W-012) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H), the mixture was heated to raise the temperature in the system to 70°C. Then, 47.4 parts by mass of styrene, 19.2 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-12) containing organic resin microparticles (A-12) containing resin (a) (A-12C) and resin (b) (A-12S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-12S) in the microparticle dispersion (W-012) as seeds. The fine particle dispersion (W-12) was adjusted so that the pure polymer content was 20%.

[0445] The organic resin fine particles (A-12) had a volume average particle diameter of 17.3 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0446] In addition, the fine particle dispersion (W-12) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (b) (A-12C). 1st The temperature was 60°C and the acid value was 0 mgKOH / g.

[0447] It was confirmed that the microparticle dispersion (W-12) contained organic resin microparticles (A-12) by drying a portion of the microparticle dispersion (W-12) and isolating the organic resin microparticles (A-12), in the same manner as in the above <Organic Resin Microparticle Production Example 1>.

[0448] Volume average particle size of organic resin fine particles (A-12), glass transition temperature Tg of resin (b) (A-12C) at the first heating time in differential scanning calorimetry 1st The measurement results of the acid value are shown in Table 3.

[0449] <Organic resin fine particle production example 21> [Production of microparticle dispersion (W-013) containing organic resin microparticles (A-13S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 578 parts by mass of styrene, 122 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-013) containing organic resin fine particles (A-13S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-013) was adjusted so that the pure polymer content was 20%.

[0450] The volume average particle diameter of the organic resin fine particles (A-13S) in the fine particle dispersion (W-013) was 15 nm. In addition, a part of the fine particle dispersion (W-013) was dried to isolate the organic resin fine particles (A-13S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-13S) were 1st The measurement results of the acid value are shown in Table 3.

[0451] <Organic resin fine particle production example 22> [Production of Microparticle Dispersion (W-13) Containing Organic Resin Microparticles (A-13)] Next, 667 parts by mass of the microparticle dispersion (W-013) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.), the mixture was heated to raise the temperature in the system to 70°C. Then, 53.3 parts by mass of styrene, 13.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-13) containing organic resin microparticles (A-13) containing resin (a) (A-13C) and resin (b) (A-13S), which are polymers in which styrene and butyl acrylate monomers are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-13S) in the microparticle dispersion (W-013) as seeds. The fine particle dispersion (W-13) was adjusted so that the pure polymer content was 20%.

[0452] The organic resin fine particles (A-13) had a volume average particle diameter of 17.3 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0453] In addition, the fine particle dispersion (W-13) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate was centrifuged and dried to isolate resin (b) (A-13C). 1st The temperature was 71°C and the acid value was 0 mgKOH / g.

[0454] <Organic resin fine particle production example 23> [Production of microparticle dispersion (W-014) containing organic resin microparticles (A-14S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 200 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 645 parts by mass of styrene, 55 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was added dropwise over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-014) containing organic resin fine particles (A-14S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-014) was adjusted so that the pure polymer content was 20%.

[0455] The volume average particle diameter of the organic resin fine particles (A-14S) in the fine particle dispersion (W-014) was 15.0 nm. A part of the fine particle dispersion (W-014) was dried to isolate the organic resin fine particles (A-14S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-14S) were 81°C and 195mgKOH / g, respectively. 1st The measurement results of the acid value are shown in Table 3.

[0456] <Organic resin fine particle production example 24> [Production of Microparticle Dispersion (W-14) Containing Organic Resin Microparticles (A-14)] Next, 667 parts by mass of the microparticle dispersion (W-014) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H), the mixture was heated to raise the temperature in the system to 70°C. Then, 59.2 parts by mass of styrene, 7.4 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-14) containing organic resin microparticles (A-14) containing resin (a) (A-14C) and resin (b) (A-14S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-14S) in the microparticle dispersion (W-014) as seeds. The fine particle dispersion (W-14) was adjusted so that the pure polymer content was 20%.

[0457] The organic resin fine particles (A-14) had a volume average particle diameter of 17.3 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0458] In addition, the fine particle dispersion (W-14) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (b) (A-14C). 1st The temperature was 80°C and the acid value was 0 mgKOH / g.

[0459] <Organic resin fine particle production example 25> [Production of microparticle dispersion (W-015) containing organic resin microparticles (A-15S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 175 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 450 parts by mass of styrene, 250 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was added dropwise over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-015) containing organic resin fine particles (A-15S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-015) was adjusted so that the pure polymer content was 20%.

[0460] The volume average particle diameter of the organic resin fine particles (A-15S) in the fine particle dispersion (W-015) was 23.0 nm. In addition, a part of the fine particle dispersion (W-015) was dried to isolate the organic resin fine particles (A-15S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-15S) were 1st The measurement results of the acid value are shown in Table 2.

[0461] <Organic resin fine particle production example 26> [Production of Microparticle Dispersion (W-15) Containing Organic Resin Microparticles (A-15)] Next, 667 parts by mass of the microparticle dispersion (W-015) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (NOF Corp., Perbutyl H), the mixture was heated to raise the temperature in the system to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-15) containing organic resin microparticles (A-15) containing resin (a) (A-15C) and resin (b) (A-15S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-15S) in the microparticle dispersion (W-015) as seeds. The fine particle dispersion (W-15) was adjusted so that the pure polymer content was 20%.

[0462] The organic resin fine particles (A-15) had a volume average particle diameter of 26.0 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0463] In addition, the fine particle dispersion (W-15) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate was centrifuged and dried to isolate resin (b) (A-15C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0464] <Organic resin fine particle production example 27> [Production of microparticle dispersion (W-016) containing organic resin microparticles (A-16S)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3710 parts by mass of water and 75 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture of 450 parts by mass of styrene, 250 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W-016) containing organic resin fine particles (A-16S) made of resin (b), which is a polymer obtained by copolymerizing a mixture of styrene, butyl acrylate, and methacrylic acid with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium. The fine particle dispersion (W-016) was adjusted so that the pure polymer content was 20%.

[0465] The volume average particle diameter of the organic resin fine particles (A-16S) in the fine particle dispersion (W-016) was 67 nm. A part of the fine particle dispersion (W-016) was dried to isolate the organic resin fine particles (A-16S). The glass transition temperature Tg 1st The volume average particle diameter and glass transition temperature (Tg) of the organic resin fine particles (A-16S) were 1st The measurement results of the acid value are shown in Table 2.

[0466] <Organic resin fine particle production example 28> [Production of Microparticle Dispersion (W-16) Containing Organic Resin Microparticles (A-16)] Next, 667 parts by mass of the microparticle dispersion (W-016) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. After adding 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.), the mixture was heated to raise the temperature in the system to 70°C. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of a 1% by mass aqueous ascorbic acid solution were dropped into the mixture over 2 hours. After the dropping, the mixture was aged at 70°C for 4 hours to obtain a microparticle dispersion (W-16) containing organic resin microparticles (A-16) containing resin (a) (A-16C) and resin (b) (A-16S), which are polymers in which styrene and butyl acrylate are copolymerized, as constituents in the same particle, using the organic resin microparticles (A-16S) in the microparticle dispersion (W-016) as seeds. The fine particle dispersion (W-16) was adjusted so that the pure polymer content was 20%.

[0467] The organic resin fine particles (A-16) had a volume average particle diameter of 76.0 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0468] In addition, the fine particle dispersion (W-16) was neutralized with a 10% by mass aqueous ammonia solution to a pH of 9.0, and the precipitate obtained by centrifugation was dried to isolate resin (b) (A-16C). 1st The temperature was 53°C and the acid value was 0 mgKOH / g.

[0469] The properties of the fine particle dispersions (W-01) to (W-016) and (W-1) to (W-16) are shown in Tables 2 and 3.

[0470] [Table 2]

[0471] [Table 3]

[0472] <Production example of crystalline polyester> [Synthesis of crystalline polyester resin] Dodecanedioic acid and 1,6-hexanediol were charged into a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 0.9, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at 180°C for 10 hours. The mixture was then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours to obtain a crystalline polyester resin.

[0473] <Production Example of Amorphous Polyester Resin> [Synthesis of amorphous polyester resin A1] Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 26.5 parts by mass of terephthalic acid, 13.5 parts by mass of an ethylene oxide 2.2 mol adduct of bisphenol A, 59.9 parts by mass of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts by mass of dibutyltin oxide were charged and reacted at normal pressure and 230° C. for 4 hours. Thereafter, the mixture was reacted under reduced pressure of 10 mmHg to 15 mmHg for 5 hours to obtain amorphous polyester resin A1.

[0474] <Production Example of Amorphous Polyester Resin> [Synthesis of amorphous polyester resin A2] Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 25.8 parts by mass of terephthalic acid, 27.8 parts by mass of adipic acid, 44.9 parts by mass of 3-methyl-1,5-pentanediol, 1.5 parts by mass of trimethylolpropane, and 0.2 parts by mass of dibutyltin oxide were charged and reacted at normal pressure and 230° C. for 4 hours. Thereafter, the mixture was reacted under reduced pressure of 10 mmHg to 15 mmHg for 5 hours to obtain an amorphous polyester resin intermediate.

[0475] Next, 90 parts by mass of the amorphous polyester resin intermediate and 10 parts by mass of isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and diluted with 100 parts by mass of ethyl acetate. The mixture was then reacted at 80° C. for 5 hours to obtain an ethyl acetate solution of amorphous polyester resin A2, which is a prepolymer.

[0476] <Example 1> [Toner manufacturing] (Preparation of Masterbatch (MB)) 1,200 parts by mass of water, 500 parts by mass of carbon black (Printex 35 manufactured by Dexa, DBP oil absorption = 42 mL / 100 mg, pH = 9.5), and 500 parts by mass of amorphous polyester resin A1 were mixed in a Henschel mixer (manufactured by Nippon Coke and Engineering Co., Ltd.), and the mixture was kneaded using two rolls at 150 ° C. for 30 minutes. Thereafter, the mixture was rolled and cooled, and pulverized with a pulperizer to obtain master batch 1.

[0477] (Preparation of wax dispersion) 50 parts by mass of paraffin wax (HNP-9, hydrocarbon wax, melting point 75°C, SP value 8.8, manufactured by Nippon Seiro Co., Ltd.) as a release agent and 450 parts by mass of ethyl acetate were charged into a container equipped with a stirring rod and a thermometer, and the temperature was raised to 80°C while stirring, and the mixture was maintained at 80°C for 5 hours. After that, the mixture was cooled to 30°C in 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) under conditions of a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain a wax dispersion.

[0478] (Preparation of Crystalline Polyester Resin Dispersion) 50 parts by mass of crystalline polyester resin and 450 parts by mass of ethyl acetate were charged into a container equipped with a stirring rod and a thermometer, and the temperature was raised to 80° C. while stirring, and the mixture was maintained at 80° C. for 5 hours. Thereafter, the mixture was cooled to 30° C. in 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex) under conditions of a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80 volume % filling of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain a crystalline polyester resin dispersion.

[0479] (Preparation of oil phase) 500 parts by mass of the wax dispersion, 300 parts by mass of an ethyl acetate solution of amorphous polyester resin A3, 500 parts by mass of the crystalline polyester resin dispersion, 700 parts by mass of amorphous polyester resin A1, 100 parts by mass of the master batch, and 2 parts by mass of isophoronediamine as a prepolymer curing agent were placed in a container and mixed at 5,000 rpm for 60 minutes with a TK Homomixer (manufactured by Primix Corporation) to obtain an oil phase.

[0480] (Preparation of aqueous phase) 938 parts by weight of water, 50 parts by weight of the aqueous dispersion (W-1) containing the organic resin fine particles (A-1), 120 parts by weight of a surfactant, and 92 parts by weight of ethyl acetate were mixed and stirred to obtain a milky white liquid, which was used as the aqueous phase.

[0481] (Emulsification / solvent removal) 1,200 parts by mass of the aqueous phase was added to a vessel containing 800 parts by mass of the oil phase, and mixed with a TK homomixer at a rotation speed of 13,000 rpm for 20 minutes to obtain an emulsified slurry. The emulsified slurry was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed at 30°C for 8 hours, and then aged at 45°C for 10 hours to obtain a dispersed slurry.

[0482] (Washing and drying) A 10% aqueous sodium hydroxide solution was added to 100 parts by mass of the dispersed slurry until the pH reached 11, and the mixture was stirred for 1 hour. Thereafter, the slurry was filtered under reduced pressure, and the following operations (1) to (4) were carried out.

[0483] (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% aqueous sodium hydroxide solution was added to the filter cake of (1), mixed with a TK homomixer (at 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid was added to the filter cake of (2), and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4): 300 parts of ion-exchanged water was added to the filter cake of (3), and the mixture was mixed in a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered.

[0484] The above steps (1) to (4) were repeated twice to obtain a filter cake.

[0485] The obtained filter cake was dried at 45°C for 48 hours in a circulating dryer and sieved through a mesh with a mesh size of 75 μm to obtain toner base particles. Approximately 0.2 g of the obtained toner base particles was weighed and put into 20 mL of methanol and stirred and dispersed. After that, ultrasonic waves were applied for 30 minutes and left to stand for 24 hours, and the supernatant was filtered through a membrane filter with a pore size of 0.2 μm. The filtered supernatant was diluted 100 times with methanol and then subjected to a liquid chromatography system (AQUITY-UPLC / SQD system, manufactured by Nihon Waters). A peak derived from an anionic surfactant containing a carboxyl group was observed by the MS detector of the liquid chromatography system, and it was confirmed that an anionic surfactant containing a carboxyl group was present on the surface of the toner base particles. In addition, the content of organic resin fine particles (A-1) contained in the toner was measured using a pyrolysis gas chromatography system (7890B, manufactured by Agilent Technologies, EGA / PY-3030D (manufactured by Frontier Labs).

[0486] (External Addition Treatment) Toner was obtained by mixing 100 parts by mass of toner base particles, 0.6 parts by mass of hydrophobic silica with an average particle size of 100 nm, 1.0 parts by mass of titanium oxide with an average particle size of 20 nm, and 0.8 parts of hydrophobic silica fine powder with an average particle size of 15 nm in a Henschel mixer. The composition of the toner raw materials is shown in Table 4.

[0487] <Preparation of carrier> 100 parts by mass of silicone resin (organo straight silicone), 5 parts by mass of γ-(2-aminoethyl)aminopropyltrimethoxysilane, and 10 parts by mass of carbon black were added to 100 parts by mass of toluene, and dispersed for 20 minutes with a homomixer to prepare a resin layer coating liquid. Using a fluidized bed type coating device, the resin layer coating liquid was applied to the surface of 1000 parts by mass of spherical magnetite with an average particle size of 50 μm to prepare a carrier.

[0488] <Preparation of developer> A developer was prepared by mixing 5 parts by mass of the toner and 95 parts by mass of the carrier using a ball mill.

[0489] <Evaluation of toner characteristics> Next, the toner properties were evaluated using each of the prepared developers as follows. The evaluation results are shown in Tables 5 and 6.

[0490] [Offset resistance] The carrier and toner were mixed so that the toner concentration was 5% by mass to obtain a developer. After the developer was put into the unit of an imageo MP C4300 (manufactured by Ricoh Co., Ltd.), a rectangular solid image of 2 cm x 15 cm was printed on PPC paper type 6000<70W>A4 T (manufactured by Ricoh Co., Ltd.) with a toner adhesion amount of 0.40 mg / cm. 2 At this time, the surface temperature of the fixing roller was changed to determine the cold offset temperature (lower limit fixing temperature) and hot offset temperature (upper limit fixing temperature) at which an offset occurred in which a residual image of a solid image was fixed in a place other than the desired place, and the offset resistance was evaluated based on the following evaluation criteria. (Cold offset evaluation criteria) ◎: The minimum fixing temperature is less than 110℃ ○: The minimum fixing temperature is 110℃ or higher and less than 120℃ △: The minimum fixing temperature is 120℃ or higher and less than 130℃ ×: The minimum fixing temperature is 130°C or higher (Hot offset evaluation criteria) ◎: The upper limit of the fixing temperature is 170℃ or more. ○: The upper limit of the fixing temperature is 160℃ or more and less than 170℃ △: The upper limit of the fixing temperature is 150℃ or more and less than 160℃ ×: The upper limit of the fixing temperature is less than 150°C.

[0491] [Heat-resistant storage stability] The toner was filled into a 50 mL glass container and left in a thermostatic chamber at 50°C for 24 hours, and then cooled to 24°C. Next, the penetration [mm] was measured using a penetration test (JISK2235-1991) to evaluate the heat-resistant storage stability. Note that a larger penetration indicates better heat-resistant storage stability. A penetration of less than 10 mm is likely to cause problems in use. (Evaluation Criteria) ◎: Penetration is 20mm or more ○: Penetration is 15mm or more and less than 20mm △: Penetration is 10mm or more and less than 15mm ×: Penetration is less than 10 mm

[0492] [Electrostatic property] 6 g of two-component developer was weighed out and placed in a sealable metal cylinder, stirred at a stirring speed of 280 rpm, and the charge amount was determined by the blow-off method, and the chargeability was evaluated based on the following evaluation criteria. The stirring times were 15 seconds (TA15), 60 seconds (TA60), and 600 seconds (TA600). TEFV200 / 300 (Powder Tech Co., Ltd.) was used as the carrier. (Evaluation Criteria) ◎: Charge amount is 36 or more ○: Charge amount is 33 or more and less than 36 △: Charge amount is 30 or more and less than 33 ×: The charge amount is less than 30

[0493] [comprehensive evaluation] The overall evaluation was based on the following evaluation criteria: A product with one ◎ or ○ for all evaluation items was rated as ◎, a product with two or more ○ marks but no problem in use was rated as ○, a product with one or more △ marks but no problem in use was rated as △, and a product with one or more × marks was rated as ×. (Evaluation Criteria) ◎:Excellent ○:Excellent △: Slightly better than conventional ×: Not practical

[0494] <Examples 2 to 4> Example 1 was carried out in the same manner as Example 1, except that the surfactant 1 used in Example 1 (preparation of the aqueous phase) was changed to any one of surfactants 2 to 4 as shown in Table 4. Surfactant 2 was used in Example 2, surfactant 3 was used in Example 3, and surfactant 4 was used in Example 4. The composition of the toner raw materials is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0495] <Examples 5 to 11> In Example 1, the same procedure as in Example 1 was carried out except that the aqueous dispersion (W-1) of organic resin fine particles (A-1) used in (preparation of aqueous phase) in Example 1 was changed to any one of the aqueous dispersions (W-2) of organic resin fine particles (A-2) to (W-7) of organic resin fine particles (A-7). In Example 5, the aqueous dispersion (W-2) of organic resin fine particles (A-2) was used. In Example 6, the aqueous dispersion (W-3) of organic resin fine particles (A-3) was used. In Example 7, the aqueous dispersion (W-4) of organic resin fine particles (A-4) was used. In Example 8, the aqueous dispersion (W-5) of organic resin fine particles (A-5) was used. In Example 9, the aqueous dispersion (W-6) of organic resin fine particles (A-6) was used. In Example 10, the aqueous dispersion (W-7) of organic resin fine particles (A-7) was used. An aqueous dispersion (W-8) of organic resin fine particles (A-8) was used in Example 11. The blending of the toner raw materials in each Example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0496] <Example 12> The same procedure as in Example 1 was repeated except that the content of the aqueous dispersion (W-1) of the organic resin fine particles (A-1) used in (Preparation of the aqueous phase) in Example 1 was changed from 50 parts by mass to 125 parts by mass. The composition of the toner raw materials in the example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0497] <Examples 13 to 19> In Example 1, the aqueous dispersion (W-1) of organic resin fine particles (A-1) used in (preparation of aqueous phase) of Example 1 was changed to any one of the aqueous dispersions (W-10) of organic resin fine particles (A-10) to (W-16) of organic resin fine particles (A-16). In Example 13, the aqueous dispersion (W-10) of organic resin fine particles (A-10) was used. In Example 14, the aqueous dispersion (W-11) of organic resin fine particles (A-11) was used. In Example 15, the aqueous dispersion (W-12) of organic resin fine particles (A-12) was used. In Example 16, the aqueous dispersion (W-13) of organic resin fine particles (A-13) was used. In Example 17, the aqueous dispersion (W-14) of organic resin fine particles (A-14) was used. In Example 18, an aqueous dispersion (W-15) of organic resin particles (A-15) was used. In Example 19, an aqueous dispersion (W-16) of organic resin particles (A-16) was used. The blending of the toner raw materials in each Example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0498] <Example 20> The same procedure as in Example 1 was repeated except that the aqueous dispersion (W-1) of organic resin particles (A-1) used in (preparation of aqueous phase) in Example 1 was changed to an aqueous dispersion (W-8) of organic resin particles (A-8) and the content was changed from 50 parts by mass to 37.5 parts by mass. The composition of the toner raw materials in this example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0499] <Example 21> The same procedure as in Example 1 was repeated except that the content of the aqueous dispersion (W-1) of the organic resin fine particles (A-1) used in (Preparation of the aqueous phase) in Example 1 was changed from 50 parts by mass to 150 parts by mass. The composition of the toner raw materials in the example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0500] <Example 22> The same procedure as in Example 1 was repeated except that the aqueous dispersion (W-1) of organic resin fine particles (A-1) used in (preparation of aqueous phase) in Example 1 was changed to an aqueous dispersion (W-8) of organic resin fine particles (A-8) and the content was changed from 50 parts by mass to 62.5 parts by mass. The composition of the toner raw materials in this example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0501] <Example 23> The same procedure as in Example 1 was repeated except that the content of the aqueous dispersion (W-1) of the organic resin fine particles (A-1) used in (preparation of the aqueous phase) in Example 1 was changed from 50 parts by mass to 37.5 parts by mass. The composition of the toner raw materials in the example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0502] <Example 24> The same procedure as in Example 1 was repeated except that the content of the aqueous dispersion (W-1) of the organic resin fine particles (A-1) used in (Preparation of the aqueous phase) in Example 1 was changed from 50 parts by mass to 75 parts by mass. The composition of the toner raw materials in the example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0503] <Example 25> The same procedure as in Example 1 was repeated except that the content of the aqueous dispersion (W-1) of the organic resin fine particles (A-1) used in (Preparation of the aqueous phase) in Example 1 was changed from 50 parts by mass to 100 parts by mass. The composition of the toner raw materials in the example is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0504] <Comparative Example 1> Example 1 was carried out in the same manner as Example 1, except that the content of water used in (preparation of aqueous phase) of Example 1 was changed from 938 parts by mass to 983 parts by mass, and surfactant 1 was changed to 75 parts by mass of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.). The composition of the toner raw materials is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0505] The acid value of the 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate used was measured using an automatic potentiometric titrator (DL-53 Titrator, Mettler Toledo) to find that the acid value was 0 mg KOH / g, confirming that the solution contained no carboxyl groups.

[0506] <Comparative Example 2> The toner of Comparative Example 1 was obtained in the same manner as in Example 1, except that the content of water used in (preparation of aqueous phase) in Example 1 was changed from 938 parts by mass to 968 parts by mass, and the surfactant 1 was changed to 90 parts by mass of a 40% aqueous solution of sodium alkanesulfonate (Latemul PS, manufactured by Kao Corporation). The composition of the toner raw materials is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0507] The acid value of the 40% aqueous solution of sodium alkanesulfonate used was measured using an automatic potentiometric titrator (DL-53 Titrator, Mettler Toledo) and was found to be 0 mg KOH / g, confirming that the solution contained no carboxyl groups.

[0508] <Comparative Example 3> The same procedure as in Example 1 was repeated, except that the aqueous dispersion (W-1) of organic resin particles (A-1) used in Example 1 (preparation of the aqueous phase) was changed to an aqueous dispersion (W-01) of organic resin particles A-1S.

[0509] <Comparative Example 4> The procedure of Example 1 was repeated, except that the aqueous dispersion (W-1) of organic resin particles (A-1) used in (preparation of the aqueous phase) of Example 1 was changed to the aqueous dispersion (W-9) of organic resin particles (A-89). However, the toner base particles could not be granulated.

[0510] <Comparative Example 5> In Example 1, the content of water used in (preparation of aqueous phase) of Example 1 was changed to 983 parts by mass, and surfactant 1 was changed to 75 parts by mass of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7, manufactured by Sanyo Chemical Industries, Ltd.). The aqueous dispersion (W-1) of organic resin fine particles (A-1) was changed to an aqueous dispersion (W-01) of organic resin fine particles A-1S. The rest was the same as in Example 1. The composition of the toner raw materials is shown in Table 4, and the evaluation results are shown in Tables 5 and 6.

[0511] The acid value of the 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate used was measured using an automatic potentiometric titrator (DL-53 Titrator, Mettler Toledo) and was found to be 0 mg KOH / g, confirming that the solution contained no carboxyl groups.

[0512] [Table 4]

[0513] [Table 5]

[0514] [Table 6]

[0515] From Tables 5 and 6, it was confirmed that the toners of Examples 1 to 25 all satisfied the conditions for use in terms of low fixability, high-temperature offset resistance, heat-resistant storage stability, and chargeability. In contrast, it was confirmed that the toners obtained in Comparative Examples 1 to 5 did not satisfy the conditions for use in terms of at least one of low fixability, high-temperature offset resistance, heat-resistant storage stability, and chargeability, or toner base particles could not be produced, and thus had practical problems.

[0516] Therefore, the toners of Examples 1 to 25 differ from the toners of Comparative Examples 1 to 5 in that they have organic resin fine particles having a core-shell structure composed of a core having a resin (a) that contains a styrene acrylic resin and does not contain a carboxyl group, and a shell having a resin (b) that contains a carboxyl group, on the surface of the toner, and an anionic surfactant containing a carboxyl group, and therefore have excellent low fixing properties, high-temperature offset resistance, heat-resistant storage stability and charging properties, and can be said to be high-quality toners.

[0517] Although the embodiment has been described above, the above embodiment is presented as an example, and the present invention is not limited to the above embodiment. The above embodiment can be implemented in various other forms, and various combinations, omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0518] 1A, 1B, 1C Image forming device 10 Electrostatic latent image carrier (photoconductor drum) 20 Charging roller (charging part) 30 Exposure device (exposure section) 40 Developing device (developing section) 50 Intermediate transfer body (intermediate transfer belt) 60 Cleaning device (cleaning section) 70 Transfer roller (transfer section) 80 Static electricity removal lamp (static electricity removal part) [Prior art documents] [Patent documents]

[0519] [Patent Document 1] JP 2005-055498 A

Claims

1. The toner contains toner base particles including a binder resin, the toner base particles are provided on their surfaces with organic resin fine particles having a core-shell structure composed of a core having a resin (a) that contains a styrene-acrylic resin and does not contain a carboxyl group and a shell having a resin (b) that contains a carboxyl group, and an anionic surfactant that contains a carboxyl group; The binder resin includes a crystalline polyester resin, The toner, wherein the anionic surfactant comprises a succinic acid derivative.

2. The glass transition point Tg of the resin (a) and the resin (b) at the first temperature rise in differential scanning calorimetry 1st 2. The toner according to claim 1, wherein the temperature is from 30° C. to 70° C.

3. 3. The toner according to claim 1, wherein the organic resin fine particles have a volume particle size of 10 nm to 100 nm.

4. 4. The toner according to claim 1, wherein the content of the organic resin fine particles is 0.2% by mass to 5% by mass based on the toner.

5. 5. The toner according to claim 4, wherein the anionic surfactant has an acid value of 100 mgKOH / g to 200 mgKOH / g.

6. A developer comprising the toner according to any one of claims 1 to 5 and a carrier.

7. A toner storage unit containing the toner according to any one of claims 1 to 5.

8. An electrostatic latent image carrier; an electrostatic latent image forming unit for forming an electrostatic latent image on the electrostatic latent image carrier; a developing section for developing the electrostatic latent image with toner to form a visible image; a transfer section for transferring the visible image onto a recording medium; a fixing unit that fixes the transferred image on the recording medium, 6. An image forming apparatus, wherein the toner is the toner according to claim 1.

9. an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image with a toner to form a visible image; a transfer step of transferring the visible image onto a recording medium; A fixing step of fixing the transferred image transferred onto the recording medium, An image forming method, wherein the toner is the toner according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Toner and method for manufacturing the same, and developer, toner-containing vessel, process cartridge, image forming apparatus and image forming method

    JP2005055498A

  • Toner, developer, image forming apparatus, and process cartridge

    JP2016164616A

  • Manufacturing method of composite resin particle

    JP2019099809A

  • Image forming apparatus and image forming method

    JP2019152856A

  • Image forming method, process cartridge, and image forming apparatus

    JP2020140113A